Photoelectric conversion element, and photoelectric conversion device having the photoelectric conversion element

JP2025036509AActive Publication Date: 2025-03-14CANON KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024227341
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2024-12-24
Publication Date
2025-03-14
Estimated Expiration
2041-02-25

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、光電変換効率に優れた光電変換素子を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036509000001_ABST
    Figure 2025036509000001_ABST
Patent Text Reader

Abstract

To provide a photoelectric conversion element excellent in photoelectric conversion efficiency.SOLUTION: A photoelectric conversion element has a first electrode 3, a second electrode 7, a photoelectric conversion layer 5 arranged between the first electrode 3 and the second electrode 7, and a reflection layer 6 arranged between one of the first electrode 3 and second electrode 7 and the photoelectric conversion layer 5. A wavelength at which the reflectance in a visible light region of the reflection layer 6 becomes maximum is within the range of a wavelength at which the optical absorption coefficient of the photoelectric conversion layer 5 is one-fifth or more of the maximum value in the visible light region.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photoelectric conversion element and a photoelectric conversion device having the photoelectric conversion element. [Background technology]

[0002] In order to solve the problem of fossil energy depletion and the global environmental problems caused by the use of fossil energy, active research is being conducted on renewable and clean alternative energy sources such as solar energy, wind power, and hydraulic power. Among them, interest in solar cells that directly convert sunlight into electrical energy is increasing. Here, a solar cell refers to a cell that absorbs light energy from sunlight and generates a current and voltage by utilizing the photovoltaic effect, in which electrons and holes are generated. Currently, np diode type silicon (Si) single crystal-based solar cells with a light energy conversion efficiency of over 20% are widely known and are actually used for solar power generation. In addition, perovskite solar cells, which use compounds with a perovskite structure in the active layer, have attracted attention from the perspective of high power generation efficiency and low cost, and many research projects are being conducted on them. Furthermore, the color of the active layer can be changed by adjusting the halogen ratio of the active layer, and it is expected that this will be applied to solar cells that are colorful and have excellent aesthetics. Non-Patent Document 1 describes a solar cell using an organic hybrid perovskite compound. It also describes that colorful solar cells can be obtained by controlling the band gap of perovskite. In Patent Document 1, TiO is used as an electron transport material. 2 Photoelectric conversion elements using SnO and ZnO are described. Patent Document 2 describes a photoelectric conversion element that uses a perovskite compound as a material for the active layer, and that uses N-alkylperylenetetracarboxylic acid diimide as an electron transporting compound in the electron transport layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2015-535390 [Patent Document 2] JP 2019-106401 A [Non-patent literature]

[0004] [Non-Patent Document 1] Jun Hong Noh et al. Chemical Management for Colorful,Efficient, and Stable Inorganic-Organic Hybrid Nanostructured Solar Cells Nano Letter.2013,13,4,1764-1769 Summary of the Invention [Problem to be solved by the invention]

[0005] The solar cells described in Non-Patent Document 1, Patent Documents 1 and 2 have room for further improvement in photoelectric conversion efficiency. The present invention has been made in view of the above problems, and an object of the present invention is to provide a photoelectric conversion element having excellent photoelectric conversion efficiency. [Means for solving the problem]

[0006] The photoelectric conversion element of the present invention has a first layer containing a perovskite compound between an anode and a cathode, and a second layer between the cathode and the first layer, The second layer is characterized by having at least one of a structure represented by the following formula (U1) and a structure represented by the following formula (U2).

[0007] [ka] (In formulas (U1) to (U2), R 1 and R 3each independently represents a substituted or unsubstituted alkylene group having 1 to 10 atoms in the main chain, or a substituted or unsubstituted phenylene group. R 2 represents a single bond, a substituted or unsubstituted alkylene group having 1 to 10 atoms in the main chain, or a substituted or unsubstituted phenylene group. The substituent of the substituted alkylene group is an alkyl group, an aryl group, a hydroxyl group, or a halogen atom. The substituent of the substituted phenylene group is a halogen atom, a nitro group, a cyano group, a hydroxyl group, an alkyl group, or a halogen-substituted alkyl group. R 9 represents a hydrogen atom or an alkyl group. A 1 represents any of the groups represented by the following formulas (A-1) to (A-6). B 1 represents a group represented by any one of the following formulas (B-1) to (B-3). D 1 is a group having 5 to 15 atoms in the main chain, as shown in the following formula (D). E 1 is a divalent group represented by any one of the following formulas (E-1) to (E-3).

[0008] [ka] (In formula (A-5), R 10 represents a hydrogen atom or an alkyl group.

[0009] [ka] (In formulas (B-1) to (B-3), R 6 and R 7each independently represents an alkylene group having 1 to 5 atoms in the main chain, an alkylene group having 1 to 5 atoms in the main chain substituted with an alkyl group having 1 to 5 carbon atoms, an alkylene group having 1 to 5 atoms in the main chain substituted with a benzyl group, an alkylene group having 1 to 5 atoms in the main chain substituted with an alkoxycarbonyl group, or an alkylene group having 1 to 5 atoms in the main chain substituted with a phenyl group. One of the carbon atoms in the main chain of the alkylene group is O, S, NH, or NR 15 (R 15 is an alkyl group. R 2 represents a single bond, a substituted or unsubstituted alkylene group having 1 to 10 atoms in the main chain, or a substituted or unsubstituted phenylene group. The substituent of the substituted alkylene group is an alkyl group, an aryl group, a hydroxyl group, or a halogen atom. The substituent of the substituted phenylene group is a halogen atom, a nitro group, a cyano group, a hydroxyl group, an alkyl group, or a halogen-substituted alkyl group. R 12 represents a hydrogen atom or an alkyl group. Ar 2 represents a substituted or unsubstituted phenylene group. The substituent of the substituted phenylene group is a halogen atom, a nitro group, a hydroxyl group, a cyano group, an alkyl group, or a halogenated alkyl group. A 1 and A 2 represents any of the groups represented by the formulas (A-1) to (A-5). E 1 is a divalent group represented by any one of the following formulas (E-1) to (E-3). o, p and q each independently represent 0 or 1, and the sum of o, p and q is 1 or more and 3 or less. The arrow indicates the R 3 )

[0010] [ka] (In formula (D), R 4 , R 5 , R 6and R 7 each independently represents an alkylene group having 1 to 5 atoms in the main chain, an alkylene group having 1 to 5 atoms in the main chain substituted with an alkyl group having 1 to 5 carbon atoms, an alkylene group having 1 to 5 atoms in the main chain substituted with a benzyl group, an alkylene group having 1 to 5 atoms in the main chain substituted with an alkoxycarbonyl group, or an alkylene group having 1 to 5 atoms in the main chain substituted with a phenyl group. One of the carbon atoms in the main chain of the alkylene group is O, S, NH, or NR 15 (R 15 is an alkyl group. Ar 1 and Ar 2 each independently represents a substituted or unsubstituted phenylene group. The substituent of the substituted phenylene group is a halogen atom, a nitro group, a hydroxyl group, a cyano group, an alkyl group, or a halogenated alkyl group. A 2 represents a group represented by any one of the formulas (A-1) to (A-6). l, m, n, o, p, and q are each independently 0 or 1, and the sum of l, m, and n, and the sum of o, p, and q are 1 or more and 3 or less.

[0011] [ka] (In formulas (E-1) to (E-3), R 101 ~R 106 , R 201 ~R 210 , R 301 ~R 304 R each independently represents a single bond, a hydrogen atom, a cyano group, a nitro group, a halogen atom, an alkoxycarbonyl group, a carboxyl group, a dialkylamino group, a hydroxyl group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heterocyclic group. 101 ~R 106 One or two of R 201 ~R 210 One or two of R 301 ~R 304One or two of represent a single bond. The substituent of the substituted alkyl group is an alkyl group, an aryl group, a halogen atom, or a carbonyl group. The substituent of the substituted aryl group or the substituted heterocyclic group is a halogen atom, a nitro group, a cyano group, an alkyl group, a halogen-substituted alkyl group, an alkoxy group, or a carbonyl group. Effect of the Invention

[0012] According to the present invention, it is possible to provide a photoelectric conversion element having excellent photoelectric conversion efficiency. [Brief description of the drawings]

[0013] [Figure 1] 1 is an example of a photoelectric conversion element according to an embodiment of the present invention. [Diagram 2] 4 is an example of color measurement according to an embodiment of the present invention. [Diagram 3] 1 is a schematic cross-sectional view in a thickness direction, illustrating a configuration of an example of a photoelectric conversion element according to an embodiment of the present invention. [Figure 4] 1 is a schematic diagram showing an example of the configuration of a photoelectric conversion element according to an embodiment of the present invention. [Diagram 5] 1 is an example of a moving object including a photoelectric conversion element according to an embodiment of the present invention. [Figure 6] 1 is an example of a building material including a photoelectric conversion element according to an embodiment of the present invention. [Figure 7] FIG. 1 is a diagram showing the spectrum of Example 1-1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] <Photoelectric conversion element> First embodiment (reference embodiment) The first embodiment of the present invention will be described in detail below. The photoelectric conversion element according to this embodiment has a first electrode, a second electrode, a photoelectric conversion layer disposed between the first electrode and the second electrode, and a reflective layer disposed between one of the first electrode and the second electrode and the photoelectric conversion layer, and is characterized in that the wavelength at which the reflectance in the visible light region of the reflective layer is maximized is within a wavelength range in which the light absorption coefficient of the photoelectric conversion layer is 1 / 5 or more of the maximum value in the visible light region. As a result of the study by the inventors, it was found that by having these configurations, a photoelectric conversion element with excellent photoelectric conversion efficiency is obtained. In this embodiment, the "photoelectric conversion layer" may be referred to as a "functional layer" or an "active layer". The photoelectric conversion layer may have a charge transport layer.

[0015] The reflective layer preferably contains particles with a volume average particle size of 50 nm to 600 nm. In this case, blue light can be reflected more strongly than other light. As a result, the amount of light absorbed by the functional layer increases, improving the photoelectric conversion efficiency.

[0016] The reflective layer strongly reflects blue light, which means that the functional layer appears red. More specifically, the L of the light reflected by the reflective layer and transmitted through the photoelectric conversion layer * c * h * Color space is 20≦L * ,30≦c * ,0≦h * ≦90. The color space is 47≦c * and 20≦L * , 42≦c * , 0≦h * ≦50, and 20≦L * , 47≦c * , 50≦h * It may be ≦90.

[0017] In this embodiment, the functional layer may have a layer that absorbs light and separates charges, that is, it may be a photoelectric conversion layer. The functional layer preferably has light absorption at a wavelength at which the reflective layer has a higher reflectance than other wavelengths. The constituent material of the functional layer may be an organic material, an inorganic material, or a material having a perovskite. It may also be a mixed layer of these materials.

[0018] The reflective layer according to this embodiment is a layer having a high reflectance at the wavelength of light having a high absorption rate of the functional layer. More specifically, the particle diameter of the particles in the reflective layer is 50 nm or more and 600 nm or less. It is preferably 70 nm or more and 500 nm or less, and more preferably 90 nm or more and 400 nm or less. The particle diameter of the particles in the reflective layer may be measured by the volume average particle diameter.

[0019] The photoelectric conversion element according to this embodiment has a first electrode, a second electrode, a photoelectric conversion layer disposed between them, and a reflective layer. The wavelength at which the reflectance of the reflective layer in the visible light region is maximized is within the range of the wavelength of light absorbed by the photoelectric conversion layer. More preferably, the wavelength at which the reflectance is maximized is within the range of wavelengths at which the light absorption coefficient of the photoelectric conversion layer is 1 / 5 or more of the maximum value in the visible light region, and even more preferably, the wavelength at which the reflectance is maximized is within the range of wavelengths at which the light absorption coefficient of the photoelectric conversion layer is half or more of the maximum value in the visible light region.

[0020] It can also be said that in the spectrum of the reflectance of the reflective layer with respect to wavelength, the wavelength corresponding to the maximum value of the reflectance is within the range of the wavelength of the light absorbed by the photoelectric conversion layer. It can also be said that the maximum peak of the spectrum is within the above range. When considering this spectrum, it may be the visible light region or the visible light region, the ultraviolet region, and the near infrared region. More specifically, it may be 250 nm or more and 1100 nm or less.

[0021] The present embodiment will be described below with reference to the drawings.

[0022] 1 is a schematic diagram showing an example of the configuration of a photoelectric conversion element 1 according to this embodiment. A first electrode 3, a charge transport layer 4, a photoelectric conversion layer 5, a reflective layer 6, and a second electrode 7 are provided on a substrate 2. The first electrode 3 and the second electrode 7 may be an anode or a cathode. A current is generated when the first electrode 3 and the second electrode 7 are connected to an external circuit. The first electrode 3 and the second electrode 7 may be disposed in interchanged positions.

[0023] As an example, the photoelectric conversion layer 5 is excited by light incident through the substrate 2, the first electrode 3, and the charge transport layer 4, and generates electrons or holes. That is, the photoelectric conversion layer 5 generates a current between the first electrode 3 and the second electrode 7. The charge transport layer 4 is a layer disposed between the photoelectric conversion layer 5 and the two electrodes, and may not be formed in some cases. A configuration in which a plurality of charge transport layers 4 and photoelectric conversion layers 5 are stacked may be used. Such a configuration may be called a tandem structure.

[0024] The photoelectric conversion element according to the present embodiment can be manufactured by preparing a coating solution for each layer described later, coating the layers in the desired order, and drying the coating solution. Examples of the coating method include dip coating, spray coating, inkjet coating, roll coating, die coating, blade coating, curtain coating, wire bar coating, ring coating, spin coater coating, etc.

[0025] [Support substrate] The supporting substrate is preferably a substrate that can form an electrode (anode or cathode) on its main surface and is made of a material that does not chemically change when forming a functional layer that constitutes a photoelectric conversion element. The supporting substrate is also simply called a substrate.

[0026] Examples of materials for the support substrate include glass, plastic, polymer film, and silicon.

[0027] In the case of a photoelectric conversion element in which light is taken in from the supporting substrate side, a substrate having high optical transparency is suitably used as the supporting substrate.

[0028] In addition, when a photoelectric conversion element is provided on an opaque support substrate, light cannot be taken in through the support substrate. Therefore, it is preferable that the electrode farther from the support substrate is transparent or semitransparent. By making the electrode farther from the support substrate transparent or semitransparent, light can be taken in through the electrode farther from the support substrate when an opaque support substrate is used.

[0029] [electrode] The electrodes are made of a conductive material, such as inorganic compounds, such as metals and metal oxides, and organic compounds, such as conductive polymers.

[0030] The electrode may be in the form of a single layer or a laminate of multiple layers.

[0031] One of the first electrode and the second electrode may be an anode and the other may be a cathode. At least one of the anode and the cathode is preferably transparent or semi-transparent.

[0032] The first electrode and the second electrode receive the charges generated in the functional layer, and the charges are extracted to the outside as electrical energy.

[0033] Examples of transparent or semitransparent electrode materials include conductive metal oxides, metals, etc., and when these materials are not transparent, they can be made into a thin film with a thickness that allows light to pass through, to make them transparent or semitransparent electrodes.Specific examples of transparent or semitransparent electrode materials include indium oxide, zinc oxide, tin oxide, and their composites ITO, IZO, FTO, NESA, gold, platinum, silver, copper, and aluminum.

[0034] The method for forming the electrodes (anode and cathode) is not particularly limited. For example, the electrodes can be formed on a layer on which the electrodes are to be formed or on a supporting substrate by vacuum deposition, sputtering, ion plating, plating, coating or the like.

[0035] [Functional Layer] The functional layer is a layer disposed between the first electrode and the second electrode. The functional layer may have a photoelectric conversion layer that converts absorbed light into electric charges. The photoelectric conversion layer may also be called an active layer. The functional layer may have a charge transport layer. The charge transport layer is called a hole transport layer or an electron transport layer depending on its form.

[0036] The functional layer may be in contact with both or either of the first electrode and the second electrode.

[0037] [Hole transport layer] The photoelectric conversion element according to this embodiment preferably has a hole transport layer provided between the photoelectric conversion layer and the anode.

[0038] The hole transport layer has a function of transporting holes from the photoelectric conversion layer to the anode. It also serves to reduce the transport of electrons from the photoelectric conversion layer to the anode, and to reduce the decrease in photoelectric conversion efficiency due to recombination of electrons and holes. The hole transport layer is preferably provided in contact with the anode.

[0039] The hole transport material forming the hole transport layer is not particularly limited, and examples thereof include inorganic materials such as CuI and CuNCS, and organic hole transport materials described in paragraphs 0209 to 0212 of JP-A No. 2001-291534. Preferred examples of the organic hole transport material include conductive polymers such as polythiophene, polyaniline, polypyrrole, and polysilane, spiro compounds in which two rings share a central atom such as C or Si to form a tetrahedral structure, aromatic amine compounds such as triarylamine, triphenylene compounds, nitrogen-containing heterocyclic compounds, and liquid crystal cyano compounds.

[0040] The hole transport material is preferably an organic hole transport material that can be applied as a solution and becomes a solid. Specific examples of the hole transport material include 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)-9,9-spirobifluorene (also known as Spiro-OMeTAD), poly(3-hexylthiophene-2,5-diyl), 4-(diethylamino)benzaldehyde diphenylhydrazone, and polyethylenedioxythiophene (PEDOT).

[0041] The thickness of the hole transport layer is not particularly limited, but is preferably 50 μm or less, more preferably 1 nm or more and 10 μm or less, even more preferably 5 nm or more and 5 μm or less, and particularly preferably 10 nm or more and 1 μm or less. This thickness can be measured by observing the cross section of the photoelectric conversion element using a scanning electron microscope (SEM) or the like.

[0042] The hole transport layer can be formed by preparing a conductive layer coating solution containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.

[0043] [Photoelectric conversion layer] The photoelectric conversion layer of the photoelectric conversion element according to this embodiment may contain a compound having a perovskite structure (perovskite compound).

[0044] The perovskite compound preferably has an organic-inorganic hybrid structure in which the organic compound and the inorganic compound are components of the perovskite structure.

[0045] Organic-inorganic perovskite compounds have the general formula RMX 3 It is preferable that the compound is represented by the following formula:

[0046] General formula RMX 3 In the above, R is an organic molecule, and C l N m H n (wherein l, m, and n are all positive integers) is preferable.

[0047] Specific examples of the R include methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, dipentylamine, dihexylamine, trimethylamine, triethylamine, tripropylamine, tributylamine, tripentylamine, trihexylamine, ethylmethylamine, methylpropylamine, butylmethylamine, methylpentylamine, hexylmethylamine, ethylpropylamine, ethylbutylamine, imidazole, azole, pyrrole, aziridine, azirine, azetidine, azeto, azole, imidazoline, carbazole, and ions thereof (e.g., methylammonium (CH3NH3), etc.), and phenethylammonium, etc. Among these, methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, and ions thereof, and phenethylammonium are preferred, and methylamine, ethylamine, propylamine, and ions thereof are more preferred.

[0048] General formula RMX 3 In the formula, M is a metal atom, such as lead, tin, zinc, titanium, antimony, bismuth, nickel, iron, cobalt, silver, copper, gallium, germanium, magnesium, calcium, indium, aluminum, manganese, chromium, molybdenum, europium, etc. These metal atoms may be used alone or in combination of two or more.

[0049] General formula RMX 3 In the formula, X is a halogen atom or a chalcogen atom, such as chlorine, bromine, iodine, sulfur, or selenium. These halogen atoms or chalcogen atoms may be used alone or in combination of two or more. Among them, halogen atoms are preferred because the organic-inorganic perovskite compound is soluble in an organic solvent by containing halogen in the structure, making it possible to apply the compound to inexpensive printing methods and the like. Furthermore, iodine is more preferred because the energy band gap of the organic-inorganic perovskite compound is narrowed.

[0050] The organic-inorganic perovskite compound preferably has a cubic crystal structure in which a metal atom M is located at the body center, an organic molecule R at each vertex, and a halogen atom or chalcogen atom X is located at the face center. Although the details are not clear, it is presumed that the above structure allows the orientation of the octahedron in the crystal lattice to be easily changed, thereby increasing the mobility of electrons in the organic-inorganic perovskite compound and improving the photoelectric conversion efficiency.

[0051] The organic-inorganic perovskite compound is preferably a crystalline semiconductor. When the organic-inorganic perovskite compound is a crystalline semiconductor, the mobility of electrons is increased, and the photoelectric conversion efficiency is improved. Note that the crystalline semiconductor refers to a semiconductor in which a scattering peak can be detected by X-ray diffraction measurement or the like.

[0052] The thickness of the organic-inorganic perovskite compound portion may be 5 nm or more and 5000 nm or less. If it is 5 nm or more, the amount of light absorption increases, and the photoelectric conversion efficiency further increases. If it is 5000 nm or less, the occurrence of regions with low charge separation efficiency can be reduced, leading to an improvement in photoelectric conversion efficiency.

[0053] The thickness of the perovskite compound portion is more preferably 10 nm or more and 1000 nm or less, and even more preferably 20 nm or more and 500 nm or less.

[0054] The active layer can be formed by preparing a conductive layer coating solution containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. The coating solution may be prepared by mixing two types of liquids with different compositions.

[0055] [Reflective layer] The photoelectric conversion element according to this embodiment has a reflective layer that reflects incident light, and is disposed between the functional layer and the first or second electrode.

[0056] The reflective layer is formed, for example, by stacking a first electrode, a charge transport layer, a photoelectric conversion layer, a reflective layer, and a second electrode in that order, and by reflecting light that has not been completely absorbed by the photoelectric conversion layer, it has the effect of promoting light absorption in the perovskite layer again and improving the light absorption efficiency of the entire element.

[0057] In order to make the light reflected by the reflective layer easily absorbed by the photoelectric conversion layer, the reflective layer contains particles having a volume average particle size of 50 nm to 600 nm. The particle size of the particles contained in the reflective layer is more preferably 70 nm to 500 nm, and particularly preferably 90 nm to 400 nm.

[0058] The refractive index of the particles is preferably from 1.3 to 3.0, more preferably from 1.8 to 3.0, and even more preferably from 2.3 to 3.0. The aspect ratio of the particles is preferably from 1.0 to 4.0, more preferably from 1.0 to 3.0, and even more preferably from 1.0 to 2.0.

[0059] The material of the particles is not particularly limited, but examples of metal compounds include zinc oxide, aluminum oxide, indium oxide, silicon oxide, zirconium oxide, tin oxide, titanium oxide, magnesium oxide, antimony oxide, bismuth oxide, barium sulfate, strontium titanate, barium titanate, potassium niobate, etc. Examples of metals include aluminum, nickel, iron, nichrome, copper, zinc, silver, etc. Examples of resin particles include acrylic resin, fluororesin, polystyrene resin, polyethylene resin, silicone resin, etc.

[0060] The particles may have a coating layer made of a conductive material. Examples of conductive materials include metal oxides, metal-based materials such as aluminum, palladium, iron, copper, and silver, and composite materials surface-treated by electrolytic treatment, spray coating, and mixed vibration. Among these, metal oxides are preferred, and metal oxides are more preferred. The metal oxide is preferably any one selected from tin oxide, zinc oxide, and titanium oxide. These metal oxides can further contribute to improving the current density by providing an oxygen deficiency structure through appropriate reduction, or by performing appropriate doping. When tin oxide is used, it is preferably doped with any one of elements selected from niobium, tantalum, phosphorus, tungsten, and fluorine. When zinc oxide is used, it is preferably doped with any one of elements selected from aluminum and gallium. When titanium oxide is used, it is preferably doped with any one of elements selected from niobium and tantalum.

[0061] In this embodiment, the aspect ratio of the particles was determined using a scanning electron microscope as follows: The particles to be measured were observed using a scanning electron microscope S-4800 manufactured by Hitachi, Ltd., and the major axis diameter and minor axis diameter of each of 100 particles were measured from the images obtained by the observation, and the arithmetic average thereof was calculated.

[0062] In this embodiment, the refractive index of the particles is defined as a value measured by CARGILL standard refractive index liquid manufactured by CARGILLE. The specific measurement method is as follows: Particles are placed on a slide glass, and the refractive index liquid is dropped. The particles and the refractive index liquid are mixed well, and a sodium lamp is irradiated from below. The outline of the particles is observed from above, and if the outline is not visible, the refractive index of the refractive index liquid and the particles are considered to be equal. In addition, in the case of a resin formed into a film, the refractive index is defined as a value measured according to JIS K7142 Plastics - Determination of refractive index.

[0063] The refractive index of the resin film is defined as a value measured using an Abbe refractometer DR-A1 (trade name, manufactured by Atago Co., Ltd.).

[0064] The reflective layer according to this embodiment may contain a binder material in addition to the particles. Examples of the binder material include polyester resin, polycarbonate resin, polyvinyl acetal resin, acrylic resin, silicone resin, epoxy resin, melamine resin, polyurethane resin, phenol resin, and alkyd resin. By using the binder material, the reflective layer can be formed densely and uniformly, the interface between the reflective layer and the active layer is formed uniformly, and the electron transport ability is improved. On the other hand, if the binder resin is excessively contained, the electron transport ability in the reflective layer may be reduced.

[0065] The weight ratio of the particles to the resin (particles / resin) in the reflective layer is preferably from 100 / 1 to 2 / 1, more preferably from 95 / 1 to 4 / 1, and even more preferably from 90 / 1 to 10 / 1.

[0066] The average thickness of the reflective layer is preferably from 50 nm to 1000 nm, and more preferably from 70 nm to 500 nm.

[0067] The reflective layer can be formed by preparing a coating solution for the reflective layer containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. Examples of the dispersion method for dispersing particles in the coating solution for the reflective layer include a method using a paint shaker, a sand mill, a ball mill, and a liquid collision type high-speed disperser. The conductive layer coating solution prepared by dispersion may be filtered to remove impurities as the coating solution for the reflective layer.

[0068] In this embodiment, the color was measured as shown in Fig. 2. That is, a coating film was formed on an aluminum sheet 21 in the order of a reflective layer 22 and a photoelectric conversion layer 23, and a spectrophotometer 24 was used to measure the L from the spectral reflectance of light received at an angle of 90 degrees to the coating surface with an irradiated light of 45 degrees to the axis perpendicular to the coating surface. * ,c * , and h *A perovskite layer can be used as the photoelectric conversion layer, and an RM200QC (manufactured by X-Rite) can be used as the spectrophotometer.

[0069] Second Embodiment (Reference Embodiment) As a result of investigations, the inventors have found that in a photoelectric conversion element having, in this order, an anode, a first layer containing a perovskite compound, a conductive second layer, and a cathode, the photoelectric conversion efficiency is improved when the second layer has conductive particles in which core particles are coated with a conductive material.

[0070] Although the detailed mechanism by which the second embodiment of the present invention exerts its effect is unclear, it is presumed to be as follows. By coating the core particles with a conductive material, an interaction occurs between the conductive material and the core particles, and the conduction band energy level of the conductive material approaches the conduction band energy level of the perovskite compound in the first layer. Therefore, it is considered that the injection of electrons from the first layer to the second layer is promoted, and the current density increases, thereby improving the photoelectric conversion efficiency.

[0071] The second embodiment of the present invention will be described in detail below. Note that the present invention is not limited to the following embodiment, and appropriate modifications and improvements to the following embodiment based on the ordinary knowledge of a person skilled in the art are also included in the scope of the present invention, provided they do not deviate from the spirit of the present invention.

[0072] FIG. 3 shows a schematic cross-sectional view of the photoelectric conversion element in the thickness direction (lamination direction), in which an anode 102, a charge transport layer 103, a first layer 104, a second layer 105, and a cathode 106 are laminated on a substrate 101. A current is generated between the anode 102 and the cathode 106 through an external circuit. The first layer 104 is a photoelectric conversion layer that is excited by light taken in from the substrate 101 side or the cathode 106 side, generates electrons or holes, and generates a current between the anode 102 and the cathode 106, and is a so-called active layer. The charge transport layer 103 is present between the first layer 104 and the two electrodes 102 and 106, but is not necessarily an essential constituent material in the photoelectric conversion element. The first layer 104 can also be formed in a tandem structure consisting of multiple layers. 3, the anode 102 is disposed on the substrate 101 side, but the cathode 106 may be disposed on the substrate 101 side, and the second layer 105, the first layer 104, the charge transport layer 103, and the anode 102 may be laminated in this order. Hereinafter, the first layer 104 will be referred to as the active layer 104.

[0073] The photoelectric conversion element of this embodiment can be manufactured by preparing the coating liquid for each layer described later, coating the layers in the desired order, and drying. In this case, the coating liquid can be applied by dip coating, spray coating, inkjet coating, roll coating, die coating, blade coating, curtain coating, wire bar coating, ring coating, spin coater coating, etc.

[0074] <substrate> The substrate 101 is preferably made of a material that can form an electrode (anode 102 in the case of FIG. 3) on its main surface and that is not chemically changed when forming a functional layer that constitutes a photoelectric conversion element. Examples of the substrate material include glass, plastic, polymer film, and silicon. When light is taken in from the substrate 101 side, a transparent material is used for the substrate 101.

[0075] <electrode> The electrodes 102 and 106 are formed of a conductive material. For example, inorganic compounds such as metals and metal oxides, and organic compounds such as conductive polymers can be used as materials for the electrodes 102 and 106. The electrodes 102 and 106 may be in the form of a single layer or a laminate of multiple layers.

[0076] When light is taken in from the substrate 101 side, a highly transparent material is preferably used as the electrode on the substrate 101 side (anode 102 in FIG. 3) so that the photoelectric conversion element can function effectively. When light is taken in from the side opposite to the substrate 101 (cathode 106 in FIG. 3), the electrode on the side opposite to the substrate 101 (cathode 106 in FIG. 3) is formed from a highly transparent material.

[0077] Examples of transparent or semitransparent electrode materials include conductive metal oxides, metals, etc., and when these materials are not transparent, they can be made into a thin film with a thickness that allows light to pass through, to form a transparent or semitransparent electrode.Specific examples of transparent or semitransparent electrode materials include indium oxide, zinc oxide, tin oxide, and their composites, such as ITO, IZO, FTO, and NESA, as well as gold, platinum, silver, copper, and aluminum.

[0078] There is no limitation on the method for forming the electrodes 102 and 106, and they can be formed by, for example, a vacuum deposition method, a sputtering method, an ion plating method, a plating method, a coating method, or the like.

[0079] <Hole transport layer> In this embodiment, it is preferable to have a hole transport layer as the charge transport layer 103 between the anode 102 and the active layer 104 .

[0080] The hole transport layer 103 has a function of transporting holes from the active layer 104 to the anode 102. It also has a function of preventing the inflow of electrons from the active layer 104 to the anode 102 and preventing a decrease in photoelectric conversion efficiency due to recombination of electrons and holes. The hole transport layer is preferably provided in contact with the anode.

[0081] Examples of the hole transport material forming the hole transport layer 103 include conductive polymers such as polythiophene, polyaniline, polypyrrole, and polysilane, spiro compounds in which two rings share a central atom such as C or Si to form a tetrahedral structure, aromatic amine compounds such as triarylamine, triphenylene compounds, nitrogen-containing heterocyclic compounds, and liquid crystalline cyano compounds.

[0082] Specifically, examples of the material include 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)-9,9-spirobifluorene (also called Spiro-OMeTAD), poly(3-hexylthiophene-2,5-diyl), 4-(diethylamino)benzoaldehyde diphenylhydrazone, polyethylenedioxythiophene (PEDOT), etc. In addition, additives such as lithium-bis(trifluoromethanesulfonyl)imide and tert-butylpyridine (TBP) may be added to the hole transport layer 103.

[0083] The thickness of the hole transport layer 103 is not particularly limited, but is preferably 1 μm or less, and more preferably 100 nm to 600 μm. This thickness can be measured by observing a cross section of the photoelectric conversion element using a scanning electron microscope (SEM) or the like.

[0084] The hole transport layer 103 can be formed by preparing a coating solution containing the above-mentioned materials and solvent, forming a coating film of the coating solution, and drying the coating solution. Examples of the solvent used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.

[0085] <Active layer> The active layer contains a compound having a perovskite structure (perovskite compound). The perovskite compound is preferably an organic-inorganic perovskite compound having an organic-inorganic hybrid structure in which an organic compound and an inorganic compound are components of the perovskite structure, and in particular, a compound represented by the general formula RMX 3 It is preferable that the compound is represented by the following formula:

[0086] General formula RMX 3 In the formula, R is an organic molecule, and examples thereof include methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, and ions thereof. M is a metal atom, and examples thereof include Cu, Ni, Mn, Fe, Co, Pd, Ge, Sn, Pb, and Eu. These metal atoms may be used alone or in combination of two or more. Furthermore, X is a halogen atom, and examples thereof include chlorine, bromine, iodine, and fluorine. These halogen atoms may be used alone or in combination of two or more.

[0087] The organic-inorganic perovskite compound is preferably a crystalline semiconductor. When the organic-inorganic perovskite compound is a crystalline semiconductor, the mobility of electrons is increased, and the photoelectric conversion efficiency is improved. Note that the crystalline semiconductor refers to a semiconductor in which a scattering peak can be detected by X-ray diffraction measurement or the like.

[0088] Furthermore, the thickness of the active layer 104 is not particularly limited, but is preferably 2 μm or less, and more preferably 200 nm to 1 μm.

[0089] The active layer 104 can be formed by preparing a coating solution containing a material that forms a perovskite compound by chemical reaction and a solvent, forming a coating film of the coating solution, and drying the coating solution. Examples of the solvent used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.

[0090] Conductive Layer In this embodiment, the conductive layer 105 provided between the active layer 104 and the cathode 106 is an electron transport layer, and has conductive particles formed by coating core particles with a conductive substance. The core particles and the conductive substance forming the coating layer have different compositions or materials.

[0091] In this embodiment, examples of the conductive material that becomes the coating layer of the conductive particles include metal oxides, metal-based materials such as aluminum, palladium, iron, copper, and silver; composite materials that have been surface-treated by electrolytic treatment, spray coating, or mixing and shaking; carbon black; and carbon-based materials. Among these, carbon black and metal oxides are preferred, and metal oxides are more preferred. The metal oxide is preferably any one selected from tin oxide, zinc oxide, and titanium oxide.

[0092] In addition, the metal oxide can further contribute to improving the current density by providing an oxygen deficiency structure through appropriate reduction or by performing appropriate doping. When tin oxide is used, it is preferably doped with any element selected from niobium, tantalum, phosphorus, tungsten, and fluorine. When zinc oxide is used, it is preferably doped with any element selected from aluminum and gallium. When titanium oxide is used, it is preferably doped with any element selected from niobium and tantalum.

[0093] The doping amount of the dopant element to the metal oxide is preferably 0.5% by mass or more and 10.0% by mass or less in the coating layer. If the doping amount is less than 0.5% by mass, the effect of improving the current density may not be sufficiently obtained. If the doping amount is more than 10.0% by mass, leakage may easily occur in the photoelectric conversion element. Furthermore, the doping amount is more preferably 1.0% by mass or more and 7.0% by mass or less in the coating layer.

[0094] In this embodiment, examples of the constituent material of the core particles of the conductive particles include metal compounds, metals, carbon black, resins, etc. Examples of metal compounds include zinc oxide, aluminum oxide, indium oxide, silicon oxide, zirconium oxide, tin oxide, titanium oxide, magnesium oxide, antimony oxide, bismuth oxide, barium sulfate, strontium titanate, barium titanate, potassium niobate, etc. Examples of metals include aluminum, nickel, iron, nichrome, copper, zinc, silver, etc. Examples of resins include acrylic resins, fluororesins, polystyrene resins, polyethylene resins, silicone resins, etc.

[0095] The core particles may have various shapes, such as a sphere, a polyhedron, an ellipsoid, a flake, or a needle. Among these, from the viewpoint of electron injection at the interface between the active layer and the conductive layer, it is preferable to use a core particle having a sphere, a polyhedron, or an ellipsoid. Furthermore, it is more preferable that the core particle has a sphere or a polyhedron close to a sphere.

[0096] In this embodiment, the aspect ratio (a / b) of the conductive particles, which is the ratio of the average major axis diameter a to the average minor axis diameter b, is preferably 3.0 or less. If the aspect ratio is 3.0 or less, the efficiency of electron injection from the active layer to the conductive layer 105 is improved, which is preferable.

[0097] In addition, the average major axis diameter a and the average minor axis diameter b of the conductive particles are preferably both 50 nm or more and 600 nm or less. If the average major axis diameter a and the average minor axis diameter b are 50 nm or more, re-aggregation of the conductive particles is unlikely to occur after preparation of the coating liquid for the conductive layer. If the average major axis diameter a and the average minor axis diameter b are 600 nm or less, the surface of the conductive layer 105 is unlikely to become rough. If the surface of the conductive layer 105 becomes rough, leakage is likely to occur. Furthermore, in this embodiment, the average major axis diameter a and the average minor axis diameter b of the conductive particles are more preferably 50 nm or more and 400 nm or less.

[0098] In this embodiment, the average major axis diameter a and the average minor axis diameter b of the conductive particles are measured using a scanning electron microscope. Specifically, the major axis diameter and minor axis diameter of each of 100 conductive particles are measured from an image obtained by observing the conductive particles to be measured using a scanning electron microscope "S-4800" manufactured by Hitachi, Ltd., and the arithmetic average thereof is calculated.

[0099] In this embodiment, the average major axis diameter and the average minor axis diameter of the core particles are preferably from 1 to 50 times, and more preferably from 5 to 20 times, the average thickness of the coating layer.

[0100] The conductive layer according to this embodiment may be formed only of the conductive particles, but may contain a binder material in addition to the conductive particles. Examples of the binder material include polyester resin, polycarbonate resin, polyvinyl acetal resin, acrylic resin, silicone resin, epoxy resin, melamine resin, polyurethane resin, phenol resin, and alkyd resin. In this embodiment, the conductive layer 105 preferably contains 20% by volume or more of the conductive particles. If the content of the conductive particles is less than 20% by volume, the distance between the conductive particles becomes long, and the current density tends to be low. Therefore, when the conductive layer 105 is composed of conductive particles and a binder resin, the content of the binder resin in the conductive layer 105 is 80% by volume or less.

[0101] The average thickness of the conductive layer 105 is preferably 0.1 μm or more and 1.0 μm or less, and more preferably 0.1 μm or more and 0.5 μm or less.

[0102] The conductive layer 105 can be formed by preparing a conductive layer coating liquid containing the conductive particles, a solvent, and, if necessary, the binder resin, forming a coating film of the coating liquid, and drying the coating liquid. Examples of the solvent used in the coating liquid include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. Examples of a dispersion method for dispersing the conductive particles in the conductive layer coating liquid include a method using a paint shaker, a sand mill, a ball mill, and a liquid collision type high-speed disperser. The conductive layer coating liquid prepared by dispersion may be filtered to remove unnecessary substances.

[0103] <Third embodiment> The third embodiment of the present invention will now be described in detail.

[0104] As a result of investigations, the present inventors have found that photoelectric conversion efficiency is improved by having a first layer containing a perovskite compound between an anode and a cathode, having a second layer between the cathode and the first layer, and the second layer having the configuration of this embodiment.

[0105] Although the detailed mechanism by which the present embodiment exerts its effect is unclear, it is presumed as follows. It is believed that the photoelectric conversion efficiency is improved by two effects when the second layer containing the electron transporting compound has any of the configurations of the present embodiment. One is believed to be due to the improvement of electron extraction by the electron transporting compound. It is believed that the photoelectric conversion efficiency is improved by combining the levels of the perovskite compound and the electron transporting compound, which allows electrons to be transferred quickly. The other is believed to promote the formation of the first layer in which the second layer is laminated as a base layer, and improve the crystallinity of the first layer. It is believed that the second layer has the configuration of the present embodiment, which makes it easy to form an interface, and the wettability of the surface is high in affinity with the first layer, promoting crystal growth. It is believed that the photoelectric conversion efficiency is improved by improving the crystallinity of the first layer, which improves light absorption and allows the generated charges to move efficiently.

[0106] The photoelectric conversion element of this embodiment has a first layer containing a perovskite compound between the anode and the cathode, and has a second layer between the cathode and the first layer.

[0107] FIG. 4 is a schematic diagram showing an example of the configuration of the photoelectric conversion element according to this embodiment. FIG. 4(A) is a plan view seen from the cathode side, FIG. 4(B) is an a-a' cross-sectional view of FIG. 4(A), and FIG. 4(C) is a b-b' cross-sectional view of FIG. 4(A). In the photoelectric conversion element of FIG. 4, an anode 211, a third layer 212, a first layer 213, a second layer 214, and a cathode 215 are laminated in this order on a substrate 216, and a current is generated between the anode 211 and the cathode 215 through an external circuit. In this example, the first layer 213 is a photoelectric conversion layer that is excited by light incident through the substrate 216, the anode 211, and the third layer 212, or the cathode 215 and the second layer 214, generates electrons or holes, and generates a current between the anode 211 and the cathode 215. The third layer 212 is a layer that exists between the first layer 213 and the anode 211, and is not necessarily an essential layer. The first layer 213 may have a plurality of layers to form a tandem structure.

[0108] The photoelectric conversion element of this embodiment can be manufactured, for example, by preparing a coating solution for each layer described later, coating the layers in the desired order, and drying the coating solution. In this case, the coating solution can be applied by dip coating, spray coating, inkjet coating, dispense coating, roll coating, die coating, blade coating, curtain coating, wire bar coating, ring coating, spin coater coating, etc.

[0109] <Board 216> A substrate that can form an electrode on its main surface and is made of a material that does not change chemically when a functional layer that constitutes a photoelectric conversion element is formed is preferably used as the substrate 216. Examples of materials for the support substrate include glass, plastic, polymer film, and silicon.

[0110] <Electrodes (anode 211, cathode 215)> The electrodes are formed of a conductive material. Examples of the material that can be used for the electrodes include inorganic compounds such as metals and metal oxides, and organic compounds such as conductive polymers. The electrodes may be in the form of a single layer or a laminate of multiple layers.

[0111] In the photoelectric conversion element of this embodiment, light incident from the electrodes is absorbed by the perovskite compound contained in the first layer 213, generating electrons and holes. The generated electrons reach the cathode 215, and the generated holes reach the anode 211, and are extracted as electric energy (current) to the outside of the photoelectric conversion element. Since the incident light needs to pass through the substrate 216 and reach the first layer 213 so that the photoelectric conversion element can function effectively, a highly transparent material is preferably used for the substrate 216 and the electrodes. In the case of a photoelectric conversion element that takes in light from the substrate 216 side, a highly light-transmitting material is preferably used for the substrate 216 and the electrodes on the substrate 216. In the case of a photoelectric conversion element that takes in light from the electrode side farther from the substrate 216, a highly light-transmitting material is preferably used for the electrode farther from the substrate 216.

[0112] Examples of transparent or semitransparent electrode materials include conductive metal oxides, metals, etc., and when these materials are not transparent, they can be made into a thin film with a thickness that allows light to pass through, to make them transparent or semitransparent electrodes. Specific examples of transparent or semitransparent electrode materials include indium oxide, zinc oxide, tin oxide, and their composites, such as ITO, IZO, FTO, and NESA, as well as gold, platinum, silver, copper, and aluminum.

[0113] There is no limitation on the method for forming the electrodes, and they can be formed by, for example, a vacuum deposition method, a sputtering method, an ion plating method, a plating method, a coating method, or the like.

[0114] <Third Layer 212> The photoelectric conversion element according to this embodiment preferably has a third layer 212 provided between the first layer 213 and the anode 211. The third layer 212 may be a hole transport layer.

[0115] The third layer 212 has a function of transporting holes from the first layer 213 to the anode 211. In addition, the third layer 212 also has a function of preventing the inflow of electrons from the first layer 213 to the anode 211, and preventing a decrease in photoelectric conversion efficiency due to recombination of electrons and holes. The third layer 212 is preferably provided in contact with the anode 211.

[0116] Examples of hole transport materials forming the third layer 212 include conductive polymers such as polythiophene, polyaniline, polypyrrole, and polysilane, spiro compounds in which two rings share a central atom such as C or Si to form a tetrahedral structure, aromatic amine compounds such as triarylamine, triphenylene compounds, nitrogen-containing heterocyclic compounds, and liquid crystal cyano compounds.Specific examples include 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)-9,9-spirobifluorene (also called Spiro-OMeTAD), poly(3-hexylthiophene-2,5-diyl), 4-(diethylamino)benzoaldehyde diphenylhydrazone, polyethylenedioxythiophene (PEDOT), and the like.

[0117] In addition, an additive such as lithium-bis(trifluoromethanesulfonyl)imide or t-butylpyridine (TBP) may be added to the third layer 212 .

[0118] The thickness of the third layer 212 is not particularly limited, but is preferably 1 μm or less, and more preferably 200 nm to 60 μm. This thickness can be measured by observing the cross section of the photoelectric conversion element using a scanning electron microscope (SEM) or the like.

[0119] The third layer 212 can be formed by preparing a conductive layer coating solution containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.

[0120] <First Layer 213> The first layer 213 contains a perovskite compound (a compound having a perovskite structure). The first layer 213 may be an active layer, a functional layer, or a photoelectric conversion layer.

[0121] The perovskite compound preferably has an organic-inorganic hybrid structure in which the organic compound and the inorganic compound are components of the perovskite structure.

[0122] Organic-inorganic perovskite compounds have the general formula RMX 3 It is preferable that the compound is represented by the following formula:

[0123] General formula RMX 3 In the formula, R is an organic molecule, such as methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, and ions thereof.

[0124] General formula RMX 3 In the formula, M is a metal atom, and examples thereof include Cu, Ni, Mn, Fe, Co, Pd, Ge, Sn, Pb, and Eu. These metal atoms may be used alone or in combination of two or more kinds.

[0125] General formula RMX 3 In the formula, X is a halogen atom, examples of which include chlorine, bromine, iodine, fluorine, etc. These halogen atoms may be used alone or in combination of two or more.

[0126] The organic-inorganic perovskite compound is preferably a crystalline semiconductor. When the organic-inorganic perovskite compound is a crystalline semiconductor, the mobility of electrons is increased, and the photoelectric conversion efficiency is improved. Note that the crystalline semiconductor refers to a semiconductor in which a scattering peak can be detected by X-ray diffraction measurement or the like.

[0127] Furthermore, the thickness of the organic / inorganic perovskite compound portion is not particularly limited, but is preferably 2 μm or less, and more preferably 200 nm or more and 1 μm or less.

[0128] The first layer 213 can be formed by preparing a conductive layer coating solution containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. In particular, aprotic polar solvents such as dimethyl sulfoxide and dimethylformamide are preferred from the viewpoint of improving the solubility of the materials of the first layer 213 and improving the crystallinity.

[0129] <Second Layer 214> The photoelectric conversion element according to this embodiment has a second layer 214 between a first layer 213 and a cathode 215. The second layer 214 may be a base layer or a conductive layer.

[0130] [First photoelectric conversion element (reference element)] In the first photoelectric conversion element, the second layer 214 has a polymer compound, and an electron transporting compound is bonded to the polymer compound.

[0131] Examples of the electron transport compound contained in the second layer 214 include oxadiazole derivatives, anthraquinodimethane and its derivatives, benzoquinone and its derivatives, naphthoquinone and its derivatives, anthraquinone and its derivatives, tetracyanoquinodimethane and its derivatives, fluorenone derivatives, diphenyldicyanoethylene and its derivatives, diphenoquinone derivatives, metal complexes of 8-hydroxyquinoline and its derivatives, polyquinoline and its derivatives, polyquinoxaline and its derivatives, polyfluorene and its derivatives, fullerenes and their derivatives, phenanthrene derivatives such as bathocuproine, naphthalenetetracarboxylic acid diimide and its derivatives, perylenetetracarboxylic acid diimide and its derivatives, pyromellitic acid diimide and its derivatives, etc. Among them, naphthalenetetracarboxylic acid diimide and its derivatives, perylenetetracarboxylic acid diimide and its derivatives, and pyromellitic acid diimide and its derivatives are preferable.

[0132] The second layer 214 may be a cured film formed by curing a curable resin, and the electron transporting compound may be bonded to a resin chain constituting the cured film.

[0133] [Second photoelectric conversion element (reference element)] In the second photoelectric conversion element, the second layer 214 has at least one of the structures represented by formulas (E-1) to (E-3) and at least one of the structures represented by formulas (P-1) to (P-5). The second layer 214 is a layer (cured layer) having at least one of the structures represented by formulas (E-1) to (E-3) and at least one of the structures represented by formulas (P-1) to (P-5). In other words, the second layer 214 contains a cured film (polymer) having at least one of the structures represented by formulas (E-1) to (E-3) and at least one of the structures represented by formulas (P-1) to (P-5).

[0134] [ka]

[0135] In formulas (E-1) to (E-3), R 101 ~R 106 , R 201 ~R 210 , R 301 ~R 304 R each independently represents a single bond, a hydrogen atom, a cyano group, a nitro group, a halogen atom, an alkoxycarbonyl group, a carboxyl group, a dialkylamino group, a hydroxyl group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heterocyclic group. 101 ~R 106 One or two of R 201 ~R 210 One or two of R 301 ~R 304One or two of the groups represent a single bond. Substituents of the substituted alkyl group include an alkyl group, an aryl group, a halogen atom, and a carbonyl group. Substituents of the substituted aryl group or the substituted heterocyclic group include a halogen atom, a nitro group, a cyano group, an alkyl group, a halogen-substituted alkyl group, an alkoxy group, and a carbonyl group.

[0136] [ka]

[0137] In formulas (P-1) to (P-5), * indicates a binding site.

[0138] The single bond may be a single bond that bonds to a resin chain that constitutes the second layer 214, and the structures represented by formulae (P-1) to (P-5) may be part of the resin chain.

[0139] Tables 1 to 5 show specific examples of formulas (E-1) to (E-3). In Tables 1 to 5, the binding sites are shown with dashed lines. The specific examples shown in Tables 1 to 5 are the same as the specific examples E-1 and E-3 shown with the corresponding numbers in Tables 6 to 11 or Tables 12 to 19. 1 Therefore, in Tables 1 to 5, the same structure may be shown more than once.

[0140] [Table 1]

[0141] [Table 2]

[0142] [Table 3]

[0143] [Table 4]

[0144] [Table 5]

[0145] The second layer 214 can be formed, for example, as follows. First, a crosslinking agent, a resin having a polymerizable functional group capable of reacting with the crosslinking agent, and an electron transporting compound having a polymerizable functional group capable of reacting with the crosslinking agent are dissolved in a solvent to prepare a coating liquid. A coating film of this coating liquid is formed and thermally cured to obtain the second layer 214. The thermal curing is preferably carried out while the coating film is drying, since this allows the reaction to occur uniformly.

[0146] [Electron transport compound] The electron transporting compound is preferably a naphthyltetracarboxydiimide derivative, a perylenetetracarboxydiimide derivative, or a pyromellitic diimide derivative. The electron transporting compound preferably has a polymerizable functional group capable of reacting with a crosslinking agent. Examples of the polymerizable functional group include a hydroxyl group, a thiol group, a carboxyl group, an amino group, an isocyanate group, and an acrylic group.

[0147] The derivative having the structure of (E-1) (derivative of an electron transport material) can be synthesized by using a known synthesis method described in, for example, U.S. Patent No. 4,442,193, U.S. Patent No. 4,992,349, U.S. Patent No. 5,468,583, and Chemistry of Materials, Vol. 19, No. 11, 2703-2705 (2007). It can also be synthesized by reacting naphthalenetetracarboxylic dianhydride, which can be purchased from Tokyo Chemical Industry Co., Ltd., Sigma-Aldrich Japan Co., Ltd., or Johnson Matthey Japan Inc., with a monoamine derivative.

[0148] In order to have a polymerizable functional group (e.g., a hydroxy group, a thiol group, an amino group, and a carboxyl group) that can react with a crosslinking agent, there are, for example, a method of directly introducing a polymerizable functional group into a derivative having the structure of (E-1), and a method of introducing a structure having a polymerizable functional group or a functional group that can be a precursor of a polymerizable functional group. Examples of the latter method include a method of introducing a functional group-containing aryl group by using a cross-coupling reaction using a palladium catalyst and a base based on a halide of a naphthyltetracarboxydiimide derivative, and a method of introducing a functional group-containing aryl group by using FeCl 3 A method of introducing a functional group-containing alkyl group using a cross-coupling reaction using a catalyst and a base, and a method of introducing an epoxy compound or CO after lithiation. 2 The former method includes, for example, a method in which a naphthalenetetracarboxylic dianhydride derivative or a monoamine derivative having a polymerizable functional group or a functional group that can be a precursor of a polymerizable functional group is used as a raw material for synthesizing a naphthyltetracarboxydiimide derivative.

[0149] Derivatives having the structure of (E-2) or (E-3) can be synthesized by using a known synthesis method described in, for example, Journal of the American Chemical Society, Vol. 129, No. 49, 15259-78 (2007). Also, they can be synthesized by reacting perylenetetracarboxylic dianhydride (E-2) or pyromellitic dianhydride (E-3), which can be purchased from Tokyo Chemical Industry Co., Ltd., Sigma-Aldrich Japan Co., Ltd., or Johnson Matthey Japan Inc., with a monoamine derivative.

[0150] Methods for introducing the polymerizable functional group into the derivative having the structure of (E-2) or (E-3) include a method for directly introducing the polymerizable functional group, and a method for introducing a structure having a polymerizable functional group or a functional group that can be a precursor of the polymerizable functional group. Examples of the latter method include a method using a cross-coupling reaction using a palladium catalyst and a base based on a halide of a perylenetetracarboxydiimide derivative or a pyromellitic diimide derivative, and a method using FeCl 3 The former method uses a cross-coupling reaction using a catalyst and a base. For example, the former method uses a perylene tetracarboxylic dianhydride derivative or a monoamine derivative having a polymerizable functional group or a functional group that can be a precursor of a polymerizable functional group as a raw material for synthesizing a perylene imide derivative.

[0151] Next, examples of the electron transporting compound having a polymerizable functional group will be given below.

[0152] [ka]

[0153] [ka]

[0154] [ka]

[0155] [ka]

[0156] [ka]

[0157] [ka]

[0158] [ka]

[0159] [ka]

[0160] [ka]

[0161] [ka]

[0162] [Third photoelectric conversion element] In the third photoelectric conversion element, the second layer 214 has at least one of the structures represented by formula (U1) and formula (U2). The second layer 214 is a layer (cured layer) having at least one of the structures represented by formula (U1) and formula (U2). In other words, the second layer 214 contains a cured film (polymer) having at least one of the structures represented by formula (U1) and formula (U2).

[0163] [ka]

[0164] In formulas (U1) to (U2), R 1 and R 3 each independently represents a substituted or unsubstituted alkylene group having 1 to 10 atoms in the main chain, or a substituted or unsubstituted phenylene group.

[0165] R 2represents a single bond, a substituted or unsubstituted alkylene group having 1 to 10 atoms in the main chain, or a substituted or unsubstituted phenylene group. The substituent of the substituted alkylene group is an alkyl group, an aryl group, a hydroxy group, or a halogen atom. The substituent of the substituted phenylene group is a halogen atom, a nitro group, a cyano group, a hydroxy group, an alkyl group, or a halogen-substituted alkyl group.

[0166] R 9 represents a hydrogen atom or an alkyl group.

[0167] A 1 represents any of the groups represented by formulae (A-1) to (A-6).

[0168] B 1 represents a group represented by any one of formulas (B-1) to (B-3).

[0169] D 1 is a group represented by formula (D) having 5 to 15 atoms in the main chain. From the viewpoint of improving photoelectric conversion efficiency, it is more preferable that the group represented by formula (D) has 10 or more and 15 or less atoms in the main chain. 1 In the formula (D), the number of atoms in the main chain refers to the shortest number of atoms between the bonds at the right and left ends. For example, a p-phenylene group has 4 atoms in the main chain. An m-phenylene group has 3 atoms in the main chain. An o-phenylene group has 2 atoms in the main chain.

[0170] E 1 is a divalent group represented by any one of formulas (E-1) to (E-3).

[0171] Here, E in formulas (U1) and (U2) 1 The right side of the represents a hydrogen atom, a substituted or unsubstituted aryl group, a substituted or unsubstituted alkyl group, or a bonding site. One of the carbon atoms in the main chain of a substituted or unsubstituted alkyl group is O, S, NH, or NR 16 (R 16is an alkyl group.) may be substituted. The substituent of the substituted aryl group may be an alkyl group, a halogen atom, a nitro group, or a cyano group. The substituent of the substituted alkyl group may be an alkyl group, an aryl group, a halogen atom, a nitro group, or a cyano group. In the case of a bonding site, E may be bonded to the structures represented by formulae (U1) and (U2) via a substituted or unsubstituted arylene group, or a substituted or unsubstituted alkylene group. 1 Except for D 1 This indicates that the compound is bound to

[0172] [ka]

[0173] In formula (A-5), R 10 represents a hydrogen atom or an alkyl group.

[0174] [ka]

[0175] In formulas (B-1) to (B-3), R 6 and R 7 each independently represents an alkylene group having 1 to 5 atoms in the main chain, an alkylene group having 1 to 5 atoms in the main chain substituted with an alkyl group having 1 to 5 carbon atoms, an alkylene group having 1 to 5 atoms in the main chain substituted with a benzyl group, an alkylene group having 1 to 5 atoms in the main chain substituted with an alkoxycarbonyl group, or an alkylene group having 1 to 5 atoms in the main chain substituted with a phenyl group. One of the carbon atoms in the main chain of the alkylene group is O, S, NH, or NR 15 (R 15 is an alkyl group.

[0176] R 2represents a single bond, a substituted or unsubstituted alkylene group having 1 to 10 atoms in the main chain, or a substituted or unsubstituted phenylene group. The substituent of the substituted alkylene group is an alkyl group, an aryl group, a hydroxy group, or a halogen atom. The substituent of the substituted phenylene group is a halogen atom, a nitro group, a cyano group, a hydroxy group, an alkyl group, or a halogen-substituted alkyl group.

[0177] R 12 represents a hydrogen atom or an alkyl group.

[0178] Ar 2 represents a substituted or unsubstituted phenylene group. The substituent of the substituted phenylene group is a halogen atom, a nitro group, a hydroxyl group, a cyano group, an alkyl group, or a halogenated alkyl group.

[0179] A 1 and A 2 represents any of the groups represented by formulae (A-1) to (A-5).

[0180] E 1 is a divalent group represented by any one of formulas (E-1) to (E-3).

[0181] o, p and q each independently represent 0 or 1, and the sum of o, p and q is 1 or more and 3 or less.

[0182] The arrow indicates R 3 This refers to the side that binds to the

[0183] E in (B-2) 1 The right side of represents a hydrogen atom, a substituted or unsubstituted aryl group, an alkyl group, a heterocyclic group, or a bonding site. Substituents of the substituted aryl group include an alkyl group, a halogen atom, and a nitro group. In the case of a bonding site, the bond is formed from the structures represented by formulae (U1) and (U2) via a substituted or unsubstituted arylene group or an alkylene group. 1 Except for D 1 In formula (B-3), CH 2The right side of the graph indicates that the compound is bonded to a side chain of a resin present in the second layer 214 .

[0184] R in formula (B-2) 6 ,R 7 ,Ar 2 ,A 2 , o, p, and q are R in formula (D), respectively. 6 ,R 7 ,Ar 2 ,A 2 , o, p, and q may be the same or different. E in formula (B-2) 1 is the E of formula (U1) and formula (U2) 1 R in formula (B-3) may be the same as or different from 2 ,A 1 are R in formula (U1) and formula (U2), respectively. 2 ,A 1 It may be the same as or different from.

[0185] [ka]

[0186] In formula (D), R 4 , R 5 , R 6 and R 7 each independently represents an alkylene group having 1 to 5 atoms in the main chain, an alkylene group having 1 to 5 atoms in the main chain substituted with an alkyl group having 1 to 5 carbon atoms, an alkylene group having 1 to 5 atoms in the main chain substituted with a benzyl group, an alkylene group having 1 to 5 atoms in the main chain substituted with an alkoxycarbonyl group, or an alkylene group having 1 to 5 atoms in the main chain substituted with a phenyl group. One of the carbon atoms in the main chain of the alkylene group is O, S, NH, or NR 15 (R 15 is an alkyl group. R 4 , R 5 , R 6 and R 7 and are each independently an alkylene group having 1 to 5 atoms in the main chain, or an alkylene group having 1 to 5 atoms in the main chain substituted with a methyl group or an ethyl group.

[0187] Ar 1 and Ar 2 each independently represents a substituted or unsubstituted phenylene group. The substituent of the substituted phenylene group is a halogen atom, a nitro group, a hydroxyl group, a cyano group, an alkyl group, or a halogenated alkyl group. Ar 1 and Ar 2 is more preferably an unsubstituted phenylene group.

[0188] A 2 represents a group represented by any one of formulas (A-1) to (A-6).

[0189] l, m, n, o, p and q each independently represent 0 or 1, and the sum of l, m and n, and the sum of o, p and q are 1 or more and 3 or less.

[0190] [ka]

[0191] In formulas (E-1) to (E-3), R 101 ~R 106 , R 201 ~R 210 , R 301 ~R 304 R each independently represents a single bond, a hydrogen atom, a cyano group, a nitro group, a halogen atom, an alkoxycarbonyl group, a carboxyl group, a dialkylamino group, a hydroxyl group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heterocyclic group. 101 ~R 106 One or two of R 201 ~R 210 One or two of R 301 ~R 304One or two of the groups represent a single bond. Substituents of the substituted alkyl group include an alkyl group, an aryl group, a halogen atom, and a carbonyl group. Substituents of the substituted aryl group or the substituted heterocyclic group include a halogen atom, a nitro group, a cyano group, an alkyl group, a halogen-substituted alkyl group, an alkoxy group, and a carbonyl group.

[0192] In the structure represented by formula (U1), R 2 is bonded to the structure X surrounded by a dashed line in the following formula. This structure X is considered to be the part corresponding to the resin chain. The same can be considered for the formula (U2).

[0193] [ka]

[0194] The present inventors believe that the photoelectric conversion efficiency is improved due to two effects of the second layer 214 having the structures represented by the formulas (U1) and (U2). 1 ) and the urethane bond improve the electron-withdrawing effect. Not only the electron-transporting compound but also the urethane bond has electron-withdrawing properties. Therefore, it is considered that the photoelectric conversion efficiency is improved by the rapid electron transfer from the perovskite compound. Another reason is that the formation of the first layer 213 in which the second layer 214 is laminated as a base layer is promoted, and the crystallinity of the first layer 213 is improved. It is considered that the second layer 214 has this configuration, so that the interface is easily formed, and the wettability of the surface is high in affinity with the first layer 213, promoting crystal growth. It is considered that the improvement in the crystallinity of the first layer 213 improves light absorption, and the generated charges can be efficiently transferred, thereby improving the photoelectric conversion efficiency.

[0195] The second layer 214 preferably contains the structures represented by formulae (U1) and (U2) in an amount of 30 mass % or more and 100 mass % or less with respect to the total mass of the second layer 214.

[0196] The content of the structure represented by formula (U1) and (U2) in the second layer 214 can be analyzed by a general analytical method. An example of the analytical method is shown below. The content of the structure represented by formula (U1) in the underlayer is measured using FT-IR and the KBr-tab method. The content of the structure represented by formula (U1) in the second layer 214 can be calculated by creating a calibration curve based on the absorption derived from the isocyanurate structure using samples in which the amount of tris(2-hydroxyethyl) isocyanurate added to KBr powder is changed. The same can be considered for formula (U2).

[0197] Furthermore, the structures represented by formulas (U1) and (U2) are solid with respect to the second layer 214. 13 This can be confirmed by measurement methods such as C-NMR measurement, mass spectrometry measurement, MS spectrum measurement by pyrolysis GC analysis, and characteristic absorption measurement by infrared spectroscopy. For example, 13 The C-NMR measurements were performed using a Chemagnetics CMX-300Infiniy. 13 C, standard substance polydimethylsiloxane, number of accumulations 8192, pulse sequence CP / MAS, DD / MAS, pulse width 2.1μsec (DD / MAS), 4.2μsec (CP / MAS), contact time 2.0msec, sample rotation speed 10kHz. Mass spectrometry is performed using a mass spectrometer (MALDI-TOF MS: Bruker Daltonics Ultraflex) under the following conditions: acceleration voltage: 20kV, mode: Reflector, molecular weight standard: fullerene C60. The molecular weight is measured and confirmed by the peak top value obtained.

[0198] In addition to the structures represented by formulae (U1) and (U2), the second layer 214 may contain various resins, crosslinking agents, organic particles, inorganic particles, metal oxide particles, leveling agents, catalysts for promoting curing, and the like, in order to improve film-forming properties and photoelectric conversion efficiency. However, the content of these is preferably less than 50 mass % and more preferably less than 20 mass % with respect to the total mass of the second layer 214. In addition, the film thickness of the second layer 214 is preferably 10 nm or more and 1.0 μm or less.

[0199] Specific examples of the structures represented by formulae (U1) and (U2) are shown below, but the present invention is not limited thereto. In Tables 6 to 11, the bond site is indicated by a dashed line. Furthermore, a single bond is indicated as "single." Furthermore, the left-right orientation of formulae (U1) and (U2) is the same as the left-right orientation of each structure in Tables 6 to 11. Furthermore, in the exemplary compounds in Tables 6 to 11, R in formulae (U1) and (U2) is 9 , R 12 are all hydrogen atoms. 6 ,R 7 ,Ar 2 ,A 2 ,o,p,q are respectively,D 1 In, R 6 ,R 7 ,Ar 2 ,A 2 , o, p, q are the same as those shown in Equations (U1) and (U2). 1 Specific examples are shown by corresponding numbers in Tables 1 to 5.

[0200] [Table 6]

[0201] [Table 7]

[0202] [Table 8]

[0203] [Table 9]

[0204] [Table 10]

[0205] [Table 11]

[0206] The second layer 214 can be formed, for example, as follows. First, an isocyanate compound (crosslinking agent), a resin having a polymerizable functional group capable of reacting with the isocyanate group of the isocyanate compound, and an electron transporting compound having a polymerizable functional group capable of reacting with the isocyanate group of the isocyanate compound are dissolved in a solvent to prepare a coating liquid. A coating film of this coating liquid is formed and thermally cured to obtain the second layer 214. The thermal curing is preferably carried out while the coating film is drying, since this allows the reaction to occur uniformly.

[0207] [Isocyanate Compound] The isocyanate compound is preferably an isocyanate compound in which the isocyanate group is protected with a blocking agent such as oxime (blocked isocyanate compound). The blocked isocyanate compound starts an addition reaction by heating together with a resin and an electron transporting compound, and the blocking agent is removed to advance the crosslinking reaction. Then, a cured product having a structure represented by formulae (U1) and (U2) is obtained.

[0208] Examples of the blocking agent include active methylene compounds such as ethyl acetate and acetylacetone, mercaptan compounds such as butyl mercaptan and dodecyl mercaptan, acid amide compounds such as acetanilide and acetic acid amide, lactam compounds such as ε-caprolactam, δ-valerolactam and γ-butyrolactam, acid imide compounds such as succinimide and maleimide, imidazole compounds such as imidazole and 2-methylimidazole, urea compounds such as urea, thiourea and ethyleneurea, oxime compounds such as formamide oxime, acetaldoxime, acetone oxime, methyl ethyl ketoxime, methyl isobutyl ketoxime and cyclohexanone oxime, and amine compounds such as diphenylaniline, aniline, carbazole, ethyleneimine and polyethyleneimine. These blocking agents can be used alone or in combination of two or more. Among these blocking agents, from the viewpoints of versatility, ease of production, workability, and heat curing temperature, oxime-based compounds such as methyl ethyl ketoxime, lactam-based compounds such as ε-caprolactam, and imidazole-based compounds such as 2-methylimidazole are preferred.

[0209] Next, examples of the isocyanate compound will be given below.

[0210] [ka]

[0211] [ka]

[0212] The isocyanate group of the isocyanate compound (number of moles = I) is preferably present in the isocyanate compound at a molar ratio (I / H) of 0.5 to 5.0 relative to the sum of the polymerizable functional groups of the resin and the polymerizable functional groups of the electron transport compound (number of moles = H). This molar ratio (I / H) of 0.5 to 5.0 is preferable because it provides good reaction efficiency between the isocyanate group and the polymerizable functional group and increases the crosslink density.

[0213] [Electron transport compound] Details of the electron transporting compound having a polymerizable functional group capable of reacting with an isocyanate group are as described above in [Electron transporting compound] in [Second photoelectric conversion element].

[0214] 〔resin〕 The polymerizable functional group of the resin is preferably a hydroxyl group, a carboxyl group, an amide group, or a thiol group. Furthermore, it is preferably a hydroxyl group or an amide group, which has a high reaction efficiency with an isocyanate group. In other words, the resin is preferably a polyol resin, a polyvinylphenol resin, a polyvinylphenol resin, or a polyamide resin having two or more hydroxyl groups or amide groups. The molecular weight of the resin is preferably in the range of weight average molecular weight (Mw) = 5,000 to 1,500,000.

[0215] The cured product having the structures represented by formulae (U1) and (U2) preferably further has a structure represented by the following formula (2). That is, the resin preferably has a structure represented by the following formula (2). When the resin has the structure represented by formula (2), the adhesion of the second layer 214 to the lower and upper layers and the thickness uniformity of the second layer 214 are improved, leading to improved photoelectric conversion efficiency.

[0216] [ka]

[0217] In formula (2), R 8 represents a substituted or unsubstituted alkyl group having 1 to 5 carbon atoms. The substituent of the substituted alkyl group is an alkyl group, an aryl group, or a halogen atom.

[0218] 〔solvent〕 The solvent for preparing the coating liquid for forming the second layer 214 can be arbitrarily selected from, for example, alcohols, aromatics, halogenated hydrocarbons, ketones, ketone alcohols, ethers, esters, etc. More specifically, for example, organic solvents such as methanol, ethanol, n-propanol, iso-propanol, n-butanol, benzyl alcohol, methyl cellosolve, ethyl cellosolve, acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, n-butyl acetate, dioxane, tetrahydrofuran, methylene chloride, chloroform, chlorobenzene, toluene, etc. These solvents can be used alone or in combination of two or more.

[0219] [Confirmation of curability] The curability of the second layer 214 can be confirmed, for example, as follows. A coating film of a coating liquid for forming the second layer 214 containing an isocyanate compound, a resin, and an electron transporting substance is formed on an aluminum sheet using a Mayer bar, and the coating film is dried by heating at 160°C for 40 minutes to form the second layer 214. The obtained second layer 214 is immersed in a mixed solvent of cyclohexanone / ethyl acetate = 1 / 1 for 2 minutes, and dried at 160°C for 5 minutes. The mass of the second layer 214 before and after immersion is confirmed to confirm that there is no elution (mass difference within ±2%).

[0220] [Fourth photoelectric conversion element (reference element)] In the fourth photoelectric conversion element, the second layer 214 has at least one of the structures represented by formula (C1) and formula (C2). The second layer 214 is a layer (cured layer) having at least one of the structures represented by formula (C1) and formula (C2). In other words, the second layer 214 contains a cured film (polymer) having at least one of the structures represented by formula (C1) and formula (C2).

[0221] [ka]

[0222] In formulas (C1) and (C2), R 11 ~R 16 and R 22 ~R 25 each independently represents a hydrogen atom, a methylene group, or -CH 2 OR 2 (R 2 represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. R represents a monovalent group represented by the formula (i), or a group represented by the formula (ii). 11 ~R 16 At least one of R 22 ~R 25 At least one of R is a group represented by formula (i), 11 ~R 16 At least one of R 22 ~R 25 At least one of the groups is a group represented by formula (ii).

[0223] R 21 represents an alkyl group, a phenyl group, or an alkyl-substituted phenyl group.

[0224] [ka]

[0225] In formula (i), R 61 represents a hydrogen atom or an alkyl group.

[0226] Y 1 represents a single bond, an alkylene group, or a phenylene group.

[0227] F 1 represents a divalent group represented by any one of formulas (F1) to (F4).

[0228] * represents the side bonded to N in formula (C1) or N in formula (C2).

[0229] [ka]

[0230] [ka]

[0231] In formula (ii), F 2 represents a divalent group represented by any one of formulas (F1) to (F4).

[0232] α represents an alkylene group having 1 to 6 main chain atoms, an alkylene group having 1 to 6 main chain atoms substituted with an alkyl group having 1 to 6 carbon atoms, an alkylene group having 1 to 6 main chain atoms substituted with a benzyl group, an alkylene group having 1 to 6 main chain atoms substituted with an alkoxycarbonyl group, or an alkylene group having 1 to 6 main chain atoms substituted with a phenyl group. One of the carbon atoms in the main chain of the alkylene group is O, S, NH, or NR 1 (R 1 is an alkyl group having 1 to 6 carbon atoms. α may be replaced by α. α is preferably an alkylene group having 1 to 5 atoms in the main chain, or an alkylene group having 1 to 5 atoms in the main chain substituted with an alkyl group having 1 to 4 carbon atoms.

[0233] β represents a phenylene group, a phenylene group substituted with an alkyl group having 1 to 6 carbon atoms, a nitro-substituted phenylene group, or a halogen-substituted phenylene group. β is preferably a phenylene group.

[0234] γ represents an alkylene group having 1 to 6 atoms in the main chain, or an alkylene group having 1 to 6 atoms in the main chain substituted with an alkyl group having 1 to 6 carbon atoms. γ is preferably an alkylene group having 1 to 5 atoms in the main chain, or an alkylene group having 1 to 5 atoms in the main chain substituted with an alkyl group having 1 to 4 carbon atoms.

[0235] r, s and t are each 0 or 1.

[0236] E 1 is a divalent group represented by any one of formulas (E-1) to (E-3).

[0237] * represents the side bonded to N in formula (C1) or N in formula (C2).

[0238] E in formula (ii) 1 When the number of atoms in the main chain other than E is 12 or less, the distance between the triazine ring and the electron transporting moiety is appropriate, and therefore smooth electron transport properties are exhibited through interaction, which is preferable in terms of improving the photoelectric conversion efficiency. 1 The number of atoms in the main chain other than the above is 2 to 9.

[0239] [ka]

[0240] In formulas (E-1) to (E-3), R 101 ~R 106 , R 201 ~R 210 , R 301 ~R 304 R each independently represents a single bond, a hydrogen atom, a cyano group, a nitro group, a halogen atom, an alkoxycarbonyl group, a carboxyl group, a dialkylamino group, a hydroxyl group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heterocyclic group. 101 ~R 106 One or two of R 201 ~R 210 One or two of R 301 ~R 304 One or two of the groups represent a single bond. Substituents of the substituted alkyl group include an alkyl group, an aryl group, a halogen atom, and a carbonyl group. Substituents of the substituted aryl group or the substituted heterocyclic group include a halogen atom, a nitro group, a cyano group, an alkyl group, a halogen-substituted alkyl group, an alkoxy group, and a carbonyl group.

[0241] The structure represented by formula (C1) has a moiety derived from a melamine compound, and the structure represented by formula (C2) has a moiety derived from a guanamine compound. The moiety derived from a melamine compound or the moiety derived from a guanamine compound is bonded to a group represented by formula (i) and a group represented by formula (ii). The group represented by formula (i) is a moiety derived from a resin. The group represented by formula (ii) has an electron transport moiety represented by any one of (E-1) to (E-3).

[0242] The present inventors believe that the photoelectric conversion efficiency is improved due to two effects of the second layer 214 having the structures represented by formulas (C1) and (C2). 1 ) and the structure represented by formula (C1) and (C2), the electron extraction effect is improved. The melamine compound and the guanamine compound have a triazine ring structure, and the triazine ring has an electron deficiency as a property of the triazine ring. It is considered that the coexistence of the electron transporting compound and the triazine ring facilitates electron transfer from the perovskite compound, improving the photoelectric conversion efficiency. The other is that the formation of the first layer 213 in which the second layer 214 is laminated as a base layer is promoted, improving the crystallinity of the first layer 213. It is considered that the second layer 214 has this structure, which makes it easy to form an interface, and the wettability of the surface is high in affinity with the first layer 213, promoting crystal growth. It is considered that the improvement in the crystallinity of the first layer 213 improves light absorption, and the generated charges can be efficiently transferred, improving the photoelectric conversion efficiency.

[0243] In the structure represented by formula (C1) and the structure represented by formula (C2), at least one group represented by formula (i) and at least one group represented by formula (ii) are bonded. When the remaining group not bonded to the group represented by formula (i) or the group represented by formula (ii) is a methylene group, it may be bonded to the melamine structure or the guanamine structure via the methylene group.

[0244] [ka]

[0245] The second layer 214 preferably contains the structure represented by formula (C1) or the structure represented by formula (C2) in an amount of 30 mass % or more and 100 mass % or less based on the total mass of the second layer 214.

[0246] The content of the structure represented by formula (C1) or (C2) in the second layer 214 can be analyzed by a general analytical method. An example of the analytical method is shown below. The content of the structure represented by formula (C1) or (C2) is measured by FT-IR and the KBr-tab method. The content of the structure represented by formula (C1) or (C2) in the second layer 214 can be calculated by creating a calibration curve based on the absorption due to the triazine ring using samples in which the amount of melamine or guanamine added to KBr powder is changed.

[0247] Furthermore, the structure represented by formula (C1) or (C2) is a solid 13 This can be confirmed by measurement methods such as C-NMR measurement, mass spectrometry measurement, MS spectrum measurement by pyrolysis GC analysis, and characteristic absorption measurement by infrared spectroscopy. For example, 13 The C-NMR measurements were performed using a Chemagnetics CMX-300Infiniy. 13 C, standard substance polydimethylsiloxane, number of accumulations 8192, pulse sequence CP / MAS, DD / MAS, pulse width 2.1μsec (DD / MAS), 4.2μsec (CP / MAS), contact time 2.0msec, sample rotation speed 10kHz. Mass spectrometry is performed using a mass spectrometer (MALDI-TOF MS: Bruker Daltonics Ultraflex) under the following conditions: acceleration voltage: 20kV, mode: Reflector, molecular weight standard: fullerene C60. The molecular weight is measured and confirmed by the peak top value obtained.

[0248] In addition to the structure represented by formula (C1) or (C2), the second layer 214 may contain various resins, crosslinking agents, organic particles, inorganic particles, metal oxide particles, leveling agents, catalysts for promoting curing, and the like, in order to improve film-forming properties and photoelectric conversion efficiency. However, the content of these is preferably less than 50 mass % and more preferably less than 20 mass % with respect to the total mass of the second layer 214. In addition, the film thickness of the second layer 214 is preferably 10 nm or more and 1.0 μm or less.

[0249] Specific examples of the structure represented by formula (C1) or (C2) are shown below, but the present invention is not limited thereto. In each specific example, in formula (ii), E 1 The number of atoms in the main chain other than the above is shown. In Tables 12 to 19, the bond site is shown with a dashed line. A single bond is shown as "single". The left and right directions of the group represented by formula (i) and the group represented by formula (ii) are the same as those of each structure in Tables 12 to 19. E in formula (ii) 1 Specific examples are shown by corresponding numbers in Tables 1 to 5.

[0250] [Table 12]

[0251] [Table 13]

[0252] [Table 14]

[0253] [Table 15]

[0254] [Table 16]

[0255] [Table 17]

[0256] [Table 18]

[0257] [Table 19]

[0258] The second layer 214 can be formed, for example, as follows. First, a coating liquid containing a melamine compound or a guanamine compound, a resin having a polymerizable functional group capable of reacting with these compounds, and an electron transport compound having a polymerizable functional group capable of reacting with these compounds is applied to form a coating film. Then, the obtained coating film is thermally cured to obtain the second layer 214.

[0259] [Melamine compounds, guanamine compounds] The melamine compound and the guanamine compound will now be described. The melamine compound or the guanamine compound is synthesized by a known method using, for example, melamine or guanamine and formaldehyde.

[0260] Specific examples of melamine compounds and guanamine compounds are shown below. Although the following specific examples show monomers, they may contain oligomers (multimers) of the monomers. From the viewpoint of improving conversion efficiency, it is preferable that the monomer is contained in an amount of 10 mass% or more based on the total mass of the monomer and multimer. The degree of polymerization of the multimer is preferably 2 or more and 100 or less. Two or more types of multimers and monomers can be mixed and used. Examples of commonly available melamine compounds include Super Melami No. 90 (manufactured by Nippon Oil & Fats Co., Ltd.), Super Beccamin® TD-139-60, L-105-60, L127-60, L110-60, J-820-60, G-821-60 (manufactured by DIC Corporation), U-Ban 2020 (Mitsui Chemicals Co., Ltd.), Sumitex Resin M-3 (Sumitomo Chemical Industries, Ltd.), Nikalac MW-30, MW-390, MX-750LM (manufactured by Nippon Carbide Co., Ltd.), etc. Examples of commonly available guanamine compounds include Super Beccamin® L-148-55, 13-535, L-145-60, TD-126 (manufactured by DIC Corporation), Nikalac BL-60, BX-4000 (manufactured by Nippon Carbide Co., Ltd.), etc.

[0261] Specific examples of the melamine compound are shown below.

[0262] [ka]

[0263] [ka]

[0264] Specific examples of the guanamine compound are shown below.

[0265] [ka]

[0266] [ka]

[0267] [ka]

[0268] The molar ratio (I:H) of the functional group (number of moles=I) possessed by the melamine compound or guanamine compound to the functional group (number of moles=H) obtained by combining the polymerizable functional groups of the resin and the electron transport compound (a compound having a structure represented by any one of (E-1) to (E-3)) is preferably 1:0.5 to 1:3.0. If the molar ratio is within this range, the proportion of functional groups that react is high, which is preferable.

[0269] [Electron transport compound] The details of the electron transporting compound having a polymerizable functional group capable of reacting with a melamine compound or a guanamine compound are as described in the above [Electron transporting compound] in the [Second photoelectric conversion element]. The electron transporting compound is represented by E 1 It comes from the structure shown below.

[0270] 〔resin〕 A resin having a polymerizable functional group capable of reacting with a melamine compound or a guanamine compound will be described. The resin has a group shown in formula (i). This resin can be obtained by polymerizing a monomer having a polymerizable functional group (hydroxyl group, thiol group, amino group, carboxyl group, and methoxy group), which can be purchased from, for example, Sigma-Aldrich Japan Co., Ltd. or Tokyo Chemical Industry Co., Ltd.

[0271] Resins can also be purchased from the public. Examples of commercially available resins include polyether polyol resins such as AQD-457 and AQD-473 manufactured by Nippon Polyurethane Industry Co., Ltd. and Sannix GP-400 and GP-700 manufactured by Sanyo Chemical Industries, Ltd., and polyester polyols such as Phthalkid W2343 manufactured by Hitachi Chemical Co., Ltd., Watersol S-118, CD-520, Beckolite M-6402-50, and M-6201-40IM manufactured by DIC Corporation, Haridip WH-1188 manufactured by Harima Chemical Co., Ltd., and ES3604 and ES6538 manufactured by Nippon U-Pica Co., Ltd. Examples of such resins include polyacrylic polyol resins such as Burnock WE-300 and WE-304 manufactured by DIC Corporation, polyvinyl alcohol resins such as Kuraray Poval PVA-203 manufactured by Kuraray Co., Ltd., polyvinyl acetal resins such as BX-1, BM-1, KS-1, and KS-5 manufactured by Sekisui Chemical Co., Ltd., polyamide resins such as Torayzin FS-350 manufactured by Nagase ChemteX Corporation, carboxyl group-containing resins such as AQUALIC manufactured by Nippon Shokubai Co., Ltd. and Finerex SG2000 manufactured by Lead City Co., Ltd., polyamine resins such as LUCKAMIDE manufactured by DIC Corporation, and polythiol resins such as QE-340M manufactured by Toray Industries, Inc. Among these, polyvinyl acetal resins and polyester polyol resins are more preferable from the viewpoint of polymerization property and uniformity of the second layer 214.

[0272] The weight average molecular weight (Mw) of the resin is preferably in the range of 5,000 to 300,000. The molecular weight of the resin can be measured, for example, by a gel permeation chromatography "HLC-8120" manufactured by Tosoh Corporation, and calculated in terms of polystyrene.

[0273] Methods for quantifying functional groups in a resin include, for example, titration of carboxyl groups with potassium hydroxide, titration of amino groups with sodium nitrite, titration of hydroxyl groups with acetic anhydride and potassium hydroxide, titration of thiol groups with 5,5'-dithiobis(2-nitrobenzoic acid), and a calibration curve method obtained from the IR spectrum of samples with different functional group introduction ratios.

[0274] Next, specific examples of the resin will be shown below.

[0275] [Table 20]

[0276] 〔solvent〕 The solvent for preparing the coating liquid for forming the second layer 214 can be arbitrarily selected from, for example, alcohols, aromatics, halogenated hydrocarbons, ketones, ketone alcohols, ethers, esters, etc. More specifically, for example, organic solvents such as methanol, ethanol, n-propanol, iso-propanol, n-butanol, benzyl alcohol, methyl cellosolve, ethyl cellosolve, acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, n-butyl acetate, dioxane, tetrahydrofuran, methylene chloride, chloroform, chlorobenzene, toluene, etc. These solvents can be used alone or in combination of two or more.

[0277] [Confirmation of curability] The curability of the second layer 214 can be confirmed, for example, as follows. A coating film of a coating liquid for forming the second layer 214 containing a melamine compound or guanamine compound, a resin, and an electron transporting substance is formed on an aluminum sheet using a Mayer bar, and the coating film is dried by heating at 160°C for 40 minutes to form the second layer 214. The obtained second layer 214 is immersed in a mixed solvent of cyclohexanone / ethyl acetate = 1 / 1 for 2 minutes, and dried at 160°C for 5 minutes. The mass of the second layer 214 before and after immersion is confirmed to ensure that no elution occurs (mass difference within ±2%).

[0278] <Photoelectric conversion device> The photoelectric conversion device has a plurality of photoelectric conversion elements according to one embodiment of the present invention. When a plurality of elements are connected, it can also be called a photoelectric conversion module. The elements may be stacked to increase the output voltage. The photoelectric conversion device also has the photoelectric conversion element according to one embodiment of the present invention and an inverter. The inverter may be a converter that converts direct current to alternating current. The photoelectric conversion device may have a storage unit connected to the photoelectric conversion element. The storage unit is not limited as long as it can store electricity. For example, a secondary battery using lithium ions or the like, an all-solid-state battery, an electric double layer capacitor, etc. can be mentioned.

[0279] FIG. 5 is an example of a moving body according to this embodiment. The moving body 30 has a photoelectric conversion element 31 according to one embodiment of the present invention and a body 32 equipped with this photoelectric conversion element. The photoelectric conversion element 31 is disposed at a position on the body 32 where it can receive external light. If the moving body 30 is an automobile, it may be disposed on the roof. The electric energy obtained by the photoelectric conversion element 31 may be used as the power source for the moving body 30 or may be used as the power source for other electric devices. The electric energy generated from the power source of the moving body 30 may be used to power the photoelectric conversion element 31. If the moving body 30 is an automobile, frictional energy generated by braking may be converted into electric energy and used to control the photoelectric conversion element 31.

[0280] The moving body 30 may be, for example, an automobile, a ship, an aircraft, or a drone. The configuration of the body 32 of the moving body 30 is not particularly limited, but it is preferably made of a high-strength material.

[0281] 6 is an example of a building material according to this embodiment. The building material may be the roof of a building. Building material 40 has photoelectric conversion element 41 according to one embodiment of the present invention, protective member 42 for protecting the photoelectric conversion element, heat dissipation member 43, and exterior 44. That is, the building material according to this embodiment has photoelectric conversion element 41 according to the present invention, and protective member 42 or heat dissipation member 43.

[0282] The building material 40 according to this embodiment may have a heat dissipation member 43 having a higher thermal conductivity than the photoelectric conversion element 41. When used on a roof or the like, the temperature of the photoelectric conversion element 41 may increase due to sunlight, and the photoelectric conversion efficiency may decrease. The use of the heat dissipation member 43 can reduce the decrease in photoelectric conversion efficiency. Examples of the heat dissipation member 43 include metal, alloy, liquid metal, and liquid resin.

[0283] The building material 40 according to this embodiment has an exterior 44. The exterior 44a and the exterior 44b may emit different colors or may be the same. The exterior 44a and the exterior 44b may be made of the same material or different materials. Paint or a transparent substrate may be used for the exterior 44. A material with low light absorption and high heat insulation is preferable.

[0284] The building material 40 according to this embodiment has a photoelectric conversion layer containing perovskite, so that it can be a building material with excellent design, and has a reflective layer, so that it has excellent photoelectric conversion efficiency. In other words, it can be a building material with excellent photoelectric conversion efficiency and vivid colors. EXAMPLES

[0285] The present invention will be described in more detail below using examples and comparative examples. The present invention is not limited to the following examples without departing from the gist of the present invention. In the following examples, "parts" are by mass unless otherwise specified.

[0286] First embodiment (reference embodiment) <Particle selection and manufacturing examples> (Particles 1 to 8: titanium oxide particles) Titanium oxide (manufactured by Teika) with a volume average particle size of 50 to 600 nm was used.

[0287] (Particle 9: Zinc oxide particle) Zinc oxide (manufactured by Hakusui Tech) with a volume average particle size of 200 nm was used.

[0288] (Particle 10: Tin oxide coated titanium oxide particle) Titanium oxide particles having a volume average particle size of 200 nm were used as the core particles.

[0289] 200 g of core particles were dispersed in water to prepare a 2 L water suspension, which was then heated to 70°C. 4 5H 2 Stannic acid solution A was prepared by dissolving 226.2 g of stannic acid (O) in 500 mL of 3 mol / L hydrochloric acid, and sodium tungstate (Na 2 WO 4 2H 2 O) 5.2 g dissolved in 500 mL of 5 mol / L sodium hydroxide solution and alkaline solution B were simultaneously added dropwise (parallel addition) over 6 hours so that the pH of the suspension became 2 to 3. After the dropwise addition was completed, the suspension was filtered, washed, and dried at 110°C for 8 hours. This dried product was subjected to a heat treatment at 650°C for 1 hour in a nitrogen gas flow (1 L / min) to produce particles 10.

[0290] (Particle 11: Nb-doped titanium oxide coated titanium oxide particle) Titanium oxide particles having a volume average particle size of 200 nm were used as the core particles.

[0291] Titanium is TiO 2 Converted to 33.7g, niobium to Nb 2 O 5 A titanium niobium sulfate solution containing 2.9 g of carbon in terms of carbon was prepared. 100 g of core particles were dispersed in pure water to prepare a 1 L suspension, which was then heated to 60°C. The titanium niobium sulfate solution and 10 mol / L sodium hydroxide were added dropwise over 3 hours so that the pH of the suspension was 2 to 3. After the entire amount was added dropwise, the pH was adjusted to approximately neutral, and a flocculant was added to precipitate the solid content. The supernatant was removed, filtered, washed, and dried at 110°C to obtain an intermediate containing 0.1 wt% of organic matter derived from the flocculant in terms of carbon. This intermediate was fired in nitrogen gas at 800°C for 1 hour to produce particles 11.

[0292] [Table 21]

[0293] <Preparation example of coating solution for reflective layer> When the reflective layer does not contain a binder material, the particles are dissolved in 1500 parts of 1-methoxy-2-propanol as a solvent to obtain a solution. 30 parts of the particles are added to this solution, which is then placed in a vertical sand mill using 1500 parts of glass beads with an average particle size of 1.0 mm as a dispersion medium, and a dispersion treatment is carried out for 4 hours under conditions of a dispersion temperature of 23±3°C and a rotation speed of 1500 rpm (circumferential speed of 5.5 m / s) to obtain a dispersion. The glass beads are removed from this dispersion using a mesh to prepare a reflective layer coating material.

[0294] When the reflective layer contains a binder material, a phenolic resin or polyamide resin as a binder material was dissolved in 1500 parts of 1-methoxy-2-propanol as a solvent to obtain a solution. The particles prepared were added to this solution at an arbitrary weight ratio to an arbitrary resin, and this was placed in a vertical sand mill using 1500 parts of glass beads with an average particle size of 1.0 mm as a dispersion medium, and a dispersion treatment was performed for 4 hours under conditions of a dispersion temperature of 23±3°C and a rotation speed of 1500 rpm (circumferential speed 5.5 m / s) to obtain a dispersion. The glass beads were removed from this dispersion using a mesh to prepare a reflective layer paint.

[0295] <Preparation example of photoelectric conversion layer paint> (Paint 1: MAPbI 3 paint) 4 parts of lead iodide and 1.4 parts of methylammonium iodide were dissolved in 4.5 parts of dimethylformamide as a solvent, and the mixture was stirred at 60° C. for 24 hours to dissolve the lead iodide.

[0296] (Paint 2: MAPbBr 3 paint) 3.4 parts of lead bromide and 1 part of methylammonium bromide were dissolved in 4.5.5 parts of dimethylformamide as a solvent, and the mixture was stirred at 60° C. for 24 hours to dissolve the lead bromide.

[0297] (Paints 3 to 5: MAPbI (1-x) Br x paint) Paint 1 and Paint 2 were mixed in the weight ratio shown in Table 22 to prepare a paint.

[0298] [Table 22]

[0299] <Example 1-1> N 2 Under atmospheric conditions, Spiro-OMeTAD (180 mg) was dissolved in chlorobenzene (1 mL) as a hole transport material on an ITO glass substrate. This chlorobenzene solution was mixed with an acetonitrile solution (37.5 μL) in which lithium-bis(trifluoromethanesulfonyl)imide (170 mg) was dissolved in acetonitrile (1 mL) and t-butylpyridine (TBP, 17.5 μL) to prepare a hole transport material solution. This was applied to the perovskite layer by spin coating. After application, the substrate was baked at 100° C. for 10 minutes to form a hole transport layer with a thickness of 300 nm.

[0300] Next, photoelectric conversion layer coating material 4 was applied onto the hole transport layer by spin coating and baked at 100° C. for 10 minutes to form a photoelectric conversion layer with a thickness of 300 nm.

[0301] Next, a coating material in which particles 6 and a phenolic resin were dispersed in a weight ratio of 80 / 1 was applied onto the photoelectric conversion layer by spin coating, and the coating was baked at 130° C. for 30 minutes to form a reflective layer having a thickness of 300 nm.

[0302] Then, a 80 nm thick, 0.09 cm area film was applied to the reflective layer. 2 A photoelectric conversion element was fabricated by forming a gold electrode on the substrate by vacuum deposition.

[0303] <Example 1-2> The photoelectric conversion layer was laminated in the same manner as in Example 1-1, and a coating material having particles 6 dispersed therein was formed into a film by spin coating, followed by baking for 30 minutes at 130° C. to form a reflective layer having a thickness of 300 nm. Thereafter, a gold electrode having a thickness of 80 nm was formed on the reflective layer by vacuum deposition to produce a photoelectric conversion element.

[0304] <Examples 1-3 to 1-19> The charge transport layer was laminated in the same manner as in Example 1-1, and the photoelectric conversion layer paint shown in Table 23 was formed into a film by spin coating and baked at 100°C for 10 minutes to form an active layer with a thickness of 300 nm. Next, the paint in which the particles shown in Table 23 were dispersed was formed into a film by spin coating and baked at 130°C for 30 minutes to form a reflective layer with a thickness of 300 nm. Thereafter, a reflective layer with a thickness of 80 nm and an area of ​​0.09 cm was applied to the reflective layer. 2 A photoelectric conversion element was fabricated by forming a gold electrode on the substrate by vacuum deposition.

[0305] <Example 1-20> The preparation was carried out in the same manner as in Example 1-1, except that the weight ratio of the particles 6 to the phenol resin was 100 / 1.

[0306] <Example 1-21> The preparation was carried out in the same manner as in Example 1-1, except that the weight ratio of the particles 6 to the phenolic resin was 2 / 1.

[0307] <Example 1-22> The preparation was carried out in the same manner as in Example 1-20, except that polyamide was used as the binder resin.

[0308] <Example 1-23> The preparation was carried out in the same manner as in Example 1-21, except that polyamide was used as the binder resin.

[0309] <Comparative Example 1-1> The preparation was carried out in the same manner as in Example 1-1, except that instead of the particles 6, titanium oxide having a volume average particle size of 30 nm was used.

[0310] <Comparative Example 1-2> The preparation was carried out in the same manner as in Example 1-2, except that instead of the particles 6, titanium oxide having a volume average particle size of 30 nm was used.

[0311] <Comparative Example 1-3> The preparation was carried out in the same manner as in Example 1-14, except that instead of the particles 6, titanium oxide having a volume average particle size of 30 nm was used.

[0312] <Evaluation> The photoelectric conversion elements obtained in each of the Examples and Comparative Examples were evaluated as follows.

[0313] (wavelength α at which the reflectance of the reflective layer in the visible light region is maximized) FIG. 7 shows the spectrum of the element of Example 1-1. FIG. 7(a) shows the reflection spectrum of the reflective layer, and FIG. 7(b) shows the absorption spectrum of the photoelectric conversion layer. FIG. 7(a) shows that the wavelength α at which the reflectance of the reflective layer in the visible light region (360 nm to 830 nm) is maximum is 656 nm. FIG. 7(b) shows that the optical absorption coefficient of the photoelectric conversion layer is a maximum value of 1.92 (AU) in the visible light region at 360 nm. Meanwhile, the optical absorption coefficient at wavelength α (656 nm) is 0.64 (AU). Therefore, in the element of Example 1-1, the wavelength α was within the wavelength range in which the optical absorption coefficient of the photoelectric conversion layer was 1 / 5 or more of the maximum value in the visible light region.

[0314] Also, in the elements of the other examples, the wavelength α was within the range of wavelengths in which the light absorption coefficient of the photoelectric conversion layer was ⅕ or more of the maximum value in the visible light region.

[0315] On the other hand, in the element of the comparative example, the wavelength α was outside the range of wavelengths in which the light absorption coefficient of the photoelectric conversion layer was ⅕ or more of the maximum value in the visible light region.

[0316] (Power generation efficiency evaluation) A power supply (KEITHLEY, Model 236) was connected between the electrodes of the photoelectric conversion element, and the intensity was 100 mW / cm 2 A constant amount of light was irradiated from the glass substrate side using a solar simulator (manufactured by Yamashita Denso Co., Ltd.), and the generated current and voltage were measured to evaluate the photoelectric conversion efficiency.

[0317] [Table 23]

[0318] As described above, the photoelectric conversion element according to the present invention exhibited a photoelectric conversion efficiency superior to that of the comparative example. Furthermore, as measured, the element not only had an excellent photoelectric conversion efficiency, but also had vivid colors.

[0319] Second embodiment (reference embodiment) [Production of conductive particles] (Conductive Particles 1) Titanium oxide particles with an average major axis diameter a and an average minor axis diameter b of 50 nm were used as the core particles. 2 Converted to 33.7g, niobium to Nb 2 O 5 A titanium niobium sulfate solution containing 2.9 g of carbon in terms of carbon was prepared. 100 g of core particles were dispersed in pure water to prepare a 1 L suspension, which was then heated to 60°C. The titanium niobium sulfate solution and 10 mol / L sodium hydroxide were added dropwise over 3 hours so that the pH of the suspension was 2 to 3. After the entire amount was added dropwise, the pH was adjusted to approximately neutral, and a flocculant was added to allow the solids to settle. The supernatant was removed, filtered, washed, and dried at 110°C to obtain an intermediate containing 0.1 mass% of organic matter derived from the flocculant in terms of carbon. This intermediate was fired in nitrogen gas at 800°C for 1 hour to obtain conductive particles 1.

[0320] (Conductive particles 2 to 6) Conductive particles 2 to 6 shown in Table 24 were prepared in the same manner as in the preparation of conductive particle 1, except that the average major axis diameter a and the average minor axis diameter b of the core particles were changed.

[0321] (Conductive particles 7) Conductive particles 7 were produced in the same manner as in the production process of conductive particles 2, except that the coating conditions were changed so that the average major axis diameter a and the average minor axis diameter b at the end of production were both 250 nm.

[0322] (Conductive particles 8) Titanium oxide particles with an average major axis diameter a and an average minor axis diameter b of 200 nm were used as the core particles. 200 g of the core particles were dispersed in water to prepare a 2 L water suspension, which was then heated to 70°C. Stannic chloride (SnCl 4 5H 2A stannic acid solution prepared by dissolving 226.2 g of O) in 500 mL of 3 mol / L hydrochloric acid and a 5 mol / L sodium hydroxide solution were simultaneously dropped (added in parallel) over a period of 6 hours so that the pH of the suspension became 2 to 3. After the dropwise addition was completed, the suspension was filtered, washed, and dried at 110°C for 8 hours. This dried material was subjected to a heat treatment at 650°C for 1 hour in a nitrogen gas flow (1 L / min) to produce conductive particles 8.

[0323] (Conductive particles 9) P 2 O 5 Conductive particles 9 shown in Table 24 were prepared in the same manner as the preparation process of conductive particles 8 above, except that orthophosphoric acid was added to the stannic acid solution so that the doping amount was 5.0 mass % in terms of conversion.

[0324] (Conductive particles 10) Ta 2 O 5 Conductive particles 10 shown in Table 24 were prepared in the same manner as the preparation process of conductive particles 8 above, except that tantalum (V) chloride was added to the stannic acid solution so that the doping amount was 5.0 mass %.

[0325] (Conductive particles 11) Nb 2 O 5 Conductive particles 11 shown in Table 24 were prepared in the same manner as the preparation process of conductive particles 8 above, except that niobium (V) chloride was added to the stannic acid solution so that the doping amount was 5.0 mass %.

[0326] (Conductive particles 12) WO 3 Conductive particles 12 shown in Table 24 were prepared in the same manner as the preparation process of conductive particles 8 above, except that sodium tungstate dihydrate was added to the stannic acid solution so that the doping amount was 5.0 mass%.

[0327] (Conductive particles 13) Conductive particles 13 shown in Table 24 were prepared in the same manner as in the preparation process of conductive particles 8 above, except that sodium fluoride was added to the stannic acid solution so that the doping amount was 1.0 mass % in terms of F.

[0328] (Conductive particles 14) Titanium oxide particles with an average major axis diameter a and an average minor axis diameter b of 200 nm were used as the core particles. 250 g of the core particles were dispersed in water to prepare a 2 L water suspension, which was then heated to 50°C. Zinc chloride (ZnCl 2 A zinc chloride aqueous solution prepared by dissolving 161.5 g of zinc chloride in 3 L of water and a 5 mol / L sodium hydroxide solution were simultaneously added dropwise (parallel addition) over a period of 2 hours so that the pH of the suspension became 10. After the addition was completed, the suspension was filtered, washed, and dried at 110° C. for 12 hours. This dried material was subjected to a heat treatment in a nitrogen gas flow (1 L / min) at 550° C. for 1 hour to produce conductive particles 14.

[0329] (Conductive particles 15) Al 2 O 3 Conductive particles 15 shown in Table 24 were prepared in the same manner as the preparation process of conductive particles 14 above, except that aluminum chloride (III) was added to the stannic acid solution so that the doping amount was 3.0 mass %.

[0330] (Conductive particles 16) Ga 2 O 3 Conductive particles 16 shown in Table 24 were prepared in the same manner as the preparation process for conductive particles 14 above, except that gallium (III) chloride was added to the stannic acid solution so that the doping amount was 3.0 mass %.

[0331] (Conductive particles 17) Conductive particles 17 shown in Table 24 were prepared in the same manner as the preparation process for conductive particles 8 above, except that barium sulfate particles having an average major axis diameter a and an average minor axis diameter b of both 300 nm were used as core particles.

[0332] (Conductive particles 18) P 2 O 5 Conductive particles 18 shown in Table 24 were prepared in the same manner as the preparation process of conductive particles 17, except that orthophosphoric acid was added to the stannic acid solution so that the doping amount was 5.0 mass % in terms of conversion.

[0333] (Conductive particles 19) Conductive particles 19 shown in Table 24 were prepared in the same manner as the preparation process for conductive particles 1, except that strontium titanate particles having an average major axis diameter a and an average minor axis diameter b of both 100 nm were used as core particles.

[0334] (Conductive particles 20) Conductive particle 20 shown in Table 24 was prepared in the same manner as the preparation process for conductive particle 1, except that barium titanate particles having an average major axis diameter a and an average minor axis diameter b of both 150 nm were used as core particles.

[0335] (Conductive particles 21) Strontium titanate particles with an average major axis diameter a and an average minor axis diameter b of 100 nm were used as the core particles. 140 mg of methylhydrogenpolysiloxane was added to 7 g of the core particles while the edge runner was operating, and the mixture was stirred for 30 minutes under a linear load of 588 N / cm (60 kg / cm). The stirring speed at this time was 22 rpm. Carbon black particles (volume average particle diameter 20 nm, volume resistivity 1.0×10 2 While the edge runner was running, 7 g of methylhydrogenpolysiloxane-coated strontium titanate particles (Ω·cm, pH 8.0) were added, and the mixture was stirred for 60 minutes at a linear load of 588 N / cm (60 kg / cm). After carbon black was attached to the surface of the methylhydrogenpolysiloxane-coated strontium titanate particles in this way, the mixture was dried at 80°C for 60 minutes in a dryer to produce conductive particles 21 shown in Table 24.

[0336] (Conductive particles 22, 23) As the core particles, strontium titanate particles having an average major axis diameter a and an average minor axis diameter b of 100 nm were used. A copper coating having a thickness of 10 nm was formed on the surface of the strontium titanate particles by electroless plating to obtain conductive particles 22 shown in Table 24. Similarly, a silver coating having a thickness of 10 nm was formed by electroless plating of silver to produce conductive particles 23 shown in Table 24.

[0337] (Conductive Particles 24) Conductive particles 24 shown in Table 24 were prepared in the same manner as the preparation process for conductive particles 8, except that silica particles having an average major axis diameter a and an average minor axis diameter b of both 150 nm were used as core particles.

[0338] (Conductive particles 25) Conductive particles 25 shown in Table 24 were prepared in the same manner as the preparation process for conductive particles 8, except that alumina particles having an average major axis diameter and an average minor axis diameter of both 250 nm were used as core particles.

[0339] (Conductive particles 26) Conductive particles 26 shown in Table 24 were prepared in the same manner as the preparation process for conductive particles 21, except that silica particles having an average major axis diameter a and an average minor axis diameter b of both 150 nm were used as core particles.

[0340] (Conductive particles 27 to 29) As conductive particles for the comparative example, tin oxide particles having an average major axis diameter a and an average minor axis diameter b of 200 nm, zinc oxide particles having an average major axis diameter a and an average minor axis diameter b of 150 nm, and carbon black particles having a volume average particle diameter of 20 nm, as shown in Table 24, were prepared.

[0341] [Table 24]

[0342] (Example 2-1) Spiro-OMeTAD (180 mg) was dissolved in chlorobenzene (1 mL) as a hole transport material. To this chlorobenzene solution, lithium-bis(trifluoromethanesulfonyl)imide (170 mg) was dissolved in acetonitrile (1 mL) to form an acetonitrile solution (37.5 μL) and t-butylpyridine (TBP, 17.5 μL) were added and mixed to prepare a hole transport material solution. 2 The hole transport material solution was applied onto an ITO glass substrate by spin coating in a 300 nm thick atmosphere, and the substrate was baked at 100° C. for 10 minutes to form a hole transport layer having a thickness of 300 nm.

[0343] Next, a coating solution for the active layer was prepared by dissolving 4 parts of lead iodide and 1.4 parts of methylammonium iodide in 4.5 parts of dimethylformamide as a solvent and stirring for 24 hours at 60° C. This was formed into a film on the hole transport layer by spin coating and baked at 100° C. for 10 minutes to form an active layer with a thickness of 300 nm.

[0344] Phenolic resin (phenolic resin monomer / oligomer) as a binding material (product name "Plyofen J-325", manufactured by DIC, resin solid content: 60% by mass, density after curing: 1.3 g / cm 2 ) was dissolved in 1500 parts of 1-methoxy-2-propanol as a solvent to obtain a solution. 30 parts of conductive particles 1 were added to this solution, which was then placed in a vertical sand mill using 1500 parts of glass beads with an average particle size of 1.0 mm as a dispersion medium, and dispersion treatment was carried out for 4 hours under conditions of a dispersion temperature of 23±3°C and a rotation speed of 1500 rpm (circumferential speed of 5.5 m / s), to obtain a dispersion. The glass beads were removed from this dispersion using a mesh, and a coating liquid for the conductive layer was prepared.

[0345] Next, the conductive layer coating solution was applied onto the active layer by spin coating, followed by baking in air at 150° C. for 10 minutes to form a conductive layer having a thickness of 500 nm.

[0346] Then, a 80 nm thick, 0.09 cm area was applied to the conductive layer. 2 A photoelectric conversion element was fabricated by forming a gold electrode on the substrate by vacuum deposition.

[0347] A power supply (KEITHLEY, Model 236) was connected between the electrodes of the photoelectric conversion element, and the intensity was 100 mW / cm 2 The photoelectric conversion efficiency was evaluated by irradiating a certain amount of light using a solar simulator (manufactured by Yamashita Denso Co., Ltd.) and measuring the generated current and voltage. The results of the short-circuit current density and photoelectric conversion efficiency are shown in Table 25.

[0348] (Examples 2-2 to 2-26) Photoelectric conversion elements were produced and their photoelectric conversion efficiency was evaluated in the same manner as in Example 2-1, except that the conductive particles used in preparing the conductive layer coating solution were changed to conductive particles 2 to 26 shown in Table 24. The results of the short-circuit current density and photoelectric conversion efficiency are shown in Table 25.

[0349] (Example 2-27) A coating solution for a conductive layer was prepared as follows.

[0350] A solution was obtained by dissolving 1 part of butyral resin (trade name: BM-1, manufactured by Sekisui Chemical Co., Ltd.) as a polyol resin and 1 part of blocked isocyanate resin (trade name: TPA-B80E, 80% solution, manufactured by Asahi Kasei Co., Ltd.) in a mixed solvent of 400 parts of methyl ethyl ketone / 700 parts of 1-butanol. 20 parts of conductive particles 2 shown in Table 24 were added to this solution, and the solution was placed in a vertical sand mill using 1100 parts of glass beads with an average particle size of 1.0 mm as a dispersion medium, and dispersion treatment was performed for 4 hours under conditions of a rotation speed of 1500 rpm (circumferential speed of 5.5 m / s) in an atmosphere of 25±3°C to prepare a coating solution for a conductive layer.

[0351] A photoelectric conversion element was prepared in the same manner as in Example 2-1, except that the above-mentioned conductive layer coating liquid was used, and the photoelectric conversion efficiency was evaluated. The results of the short-circuit current density and the photoelectric conversion efficiency are shown in Table 25.

[0352] (Example 2-28) A photoelectric conversion element was produced and its photoelectric conversion efficiency was evaluated in the same manner as in Example 2-27, except that the conductive particles used in preparing the conductive layer coating solution were changed to conductive particles 9 shown in Table 24. The results of the short-circuit current density and photoelectric conversion efficiency are shown in Table 25.

[0353] (Example 2-29) A photoelectric conversion element was produced in the same manner as in Example 2-1, except that no phenolic resin was used in preparing the coating solution for the conductive layer, and conductive particles 2 shown in Table 24 were used as the conductive particles, and the photoelectric conversion efficiency was evaluated. The results of the short-circuit current density and photoelectric conversion efficiency are shown in Table 25.

[0354] (Comparative Examples 2-1 to 2-3) A photoelectric conversion element was produced and its photoelectric conversion efficiency was evaluated in the same manner as in Example 2-1, except that the conductive particles used in preparing the conductive layer coating solution were changed to any one of conductive particles 27 to 29 shown in Table 24. The results of the short-circuit current density and photoelectric conversion efficiency are shown in Table 25.

[0355] In the elements of Comparative Examples 2-1 and 2-2, the wavelength α at which the reflectance of the reflective layer in the visible light region was maximized was outside the range of wavelengths at which the light absorption coefficient of the photoelectric conversion layer was 1 / 5 or more of the maximum value in the visible light region.

[0356] [Table 25]

[0357] Third Embodiment <Example 3-1> 3.27 parts of exemplary compound (E-1-1) as an electron transporting compound, 6.2 parts of exemplary compound (I-8) as an isocyanate compound, and 1.29 parts of butyral resin (product name: BM-1, manufactured by Sekisui Chemical Co., Ltd.) as a resin were dissolved in a mixed solution of 50 parts of methyl ethyl ketone and 50 parts of dimethylacetamide. 0.031 parts of dioctyltin diuralate as a catalyst were added to the obtained solution to prepare a coating solution for an underlayer as the second layer 214. This coating solution was applied by spin coating onto an FTO glass substrate as the substrate 216 on which the cathode 215 was formed. After application, the solution was heated at 160° C. for 30 minutes to polymerize (cure) the solution, thereby forming an underlayer having a thickness of 500 nm.

[0358] Next, lead iodide was dissolved in N,N-dimethylformamide (DMF) as a metal halide compound to prepare a 1M solution. This was then formed on the underlayer by spin coating. Furthermore, methylammonium iodide was dissolved in 2-propanol as an amine compound to prepare a 1M solution. The sample on which the lead iodide film was formed was immersed in this solution, and then baked in air at 100°C for 10 minutes to form a perovskite layer as the first layer 213 having a thickness of 500 nm.

[0359] Next, Spiro-OMeTAD (180 mg) as a hole transport material was dissolved in chlorobenzene (1 mL). This chlorobenzene solution was mixed with an acetonitrile solution (37.5 μL) in which lithium-bis(trifluoromethanesulfonyl)imide (170 mg) was dissolved in acetonitrile (1 mL) and t-butylpyridine (TBP, 17.5 μL) to prepare a hole transport material solution. This was applied onto the perovskite layer by spin coating. After application, the material was baked in air at 100° C. for 10 minutes to form a hole transport layer as the third layer 212 having a thickness of 300 nm.

[0360] Thereafter, a gold electrode serving as an anode 211 having a thickness of 80 nm was formed on the hole transport layer by vacuum deposition to prepare a photoelectric conversion element.

[0361] [evaluation] [Structure of the base layer] The structure of the underlayer was analyzed as follows. The photoelectric conversion element for structural analysis of the underlayer was immersed in a chlorobenzene solvent for 5 minutes, and ultrasonic waves were applied to peel off the hole transport layer. Next, the perovskite layer was polished using wrapping tape (C2000: manufactured by Fuji Photo Film Co., Ltd.), and then dried at 100°C for 10 minutes to prepare a photoelectric conversion element for structural analysis of the underlayer. It was confirmed using the FTIR-ATR method that no components of the hole transport layer and perovskite layer remained on the surface of the underlayer. The central part of the photoelectric conversion element was cut into a 5 mm square to prepare a sample for structural analysis of the underlayer. The above-mentioned solid 13 The structure represented by formula (U1) (specific examples of Tables 1 to 11) and D, which were confirmed by C-NMR measurement, mass spectrometry measurement, MS spectrum measurement by pyrolysis GC analysis, and characteristic absorption measurement by infrared spectroscopy, 1 The number of atoms in the main chain of the structure is shown in Table 26.

[0362] [Power generation efficiency evaluation] A power supply (KEITHLEY, Model 236) was connected between the electrodes of the photoelectric conversion element, and the intensity was 100 mW / cm 2The photoelectric conversion efficiency was evaluated by irradiating a certain amount of light using a solar simulator (manufactured by Yamashita Denso Co., Ltd.) and measuring the generated current and voltage. The results of the short-circuit current density and photoelectric conversion efficiency are shown in Table 26.

[0363] <Examples 3-2 to 3-73> A photoelectric conversion element was prepared and evaluated in the same manner as in Example 3-1, except that in the coating solution for the undercoat layer used in Example 3-1, the electron transport compound and the isocyanate compound were changed as shown in Tables 26 and 27.

[0364] <Comparative Examples 3-1 to 3-3> A photoelectric conversion element was prepared and evaluated in the same manner as in Example 3-1, except that in the coating solution for the undercoat layer used in Example 3-1, only an electron transporting compound was used, and neither an isocyanate compound nor a resin was used, and the changes were made as shown in Table 28.

[0365] <Comparative Example 3-4> A photoelectric conversion element was prepared and evaluated in the same manner as in Example 3-1, except that in the coating solution for the undercoat layer used in Example 3-1, an isocyanate compound and a resin were used instead of an electron transport compound, as shown in Table 28.

[0366] [Table 26]

[0367] [Table 27]

[0368] [Table 28]

[0369] In Tables 26 to 28, "parts by mass of electron transport compound" refers to the content (parts by mass) of the electron transport compound in the undercoat layer coating liquid. "parts by mass of isocyanate compound" refers to the content (parts by mass) of the isocyanate compound in the undercoat layer coating liquid. "parts by mass of resin" refers to the content (parts by mass) of the resin in the undercoat layer coating liquid.

[0370] In comparison between the examples and the comparative examples, as in Comparative Examples 3-1 to 3-3, when the underlayer was formed only with an electron transporting compound, dissolution of the underlayer was observed when the perovskite layer was applied, and the film properties were significantly deteriorated. Therefore, it is considered that the characteristics as a photoelectric conversion element were not measured. In addition, in Comparative Example 3-4, since there is no electron transporting compound, it is considered that electrons cannot move from the perovskite layer.

[0371] <Example 3-74 (Reference Example)> 5 parts of electron transport compound (E-1-8), 3.5 parts of melamine compound (C1-3), 3.4 parts of resin 1, and 0.1 parts of dodecylbenzenesulfonic acid as a catalyst were dissolved in a mixed solvent of 100 parts of dimethylacetamide and 100 parts of methyl ethyl ketone to prepare a coating solution for the underlayer. This coating solution was applied onto an FTO glass substrate by spin coating. After application, the substrate was heated at 160°C for 30 minutes to polymerize (cure) the solution, thereby forming a 500 nm thick underlayer. Thereafter, a photoelectric conversion element was prepared and evaluated in the same manner as in Example 3-1.

[0372] <Examples 3-75 to 3-141 (Reference Examples)> A photoelectric conversion element was prepared and evaluated in the same manner as in Example 3-74, except that in the coating solution for the undercoat layer used in Example 3-74, the electron transport compound, the melamine compound, and the guanamine compound were changed as shown in Tables 29 and 30.

[0373] <Comparative Examples 3-5 to 3-7> In the coating solution for the undercoat layer used in Example 3-74, only the electron transporting compound was used, and no melamine compound, guanamine compound, or resin was used, as shown in Table 31. A photoelectric conversion element was prepared and evaluated in the same manner as in Example 3-74, except that the coating solution was changed as shown in Table 31.

[0374] <Comparative Example 3-8> A photoelectric conversion element was prepared and evaluated in the same manner as in Example 3-74, except that in the coating solution for the undercoat layer used in Example 3-74, no electron transporting compound was used, and a melamine compound, a guanamine compound, and a resin were used as shown in Table 31.

[0375] [Table 29]

[0376] [Table 30]

[0377] [Table 31]

[0378] In Tables 29 to 31, the parts by mass of the electron transporting compound indicates the content (parts by mass) of the electron transporting compound in the coating liquid for the undercoat layer. The parts by mass of the melamine compound and the guanamine compound indicate the content (parts by mass) of the melamine compound and the guanamine compound in the coating liquid for the undercoat layer. The parts by mass of the resin indicates the content (parts by mass) of the resin in the coating liquid for the undercoat layer.

[0379] In comparison between the examples and the comparative examples, as in Comparative Examples 3-5 to 3-7, when the underlayer was formed only with an electron transporting compound, dissolution of the underlayer was observed when the perovskite layer was applied, and the film properties were significantly deteriorated. Therefore, it is considered that the characteristics as a photoelectric conversion element were not measured. In addition, in Comparative Example 3-8, since there is no electron transporting compound, it is considered that electrons cannot move from the perovskite layer. [Explanation of symbols]

[0380] 2: substrate, 3: first electrode, 4: charge transport layer, 5: photoelectric conversion layer, 6: reflective layer, 7: second electrode 102: anode, 104: first layer, 105: second layer, 106: cathode 211: anode, 212: third layer, 213: first layer, 214: second layer, 215: cathode, 216: substrate

Claims

1. A first layer containing a perovskite compound is provided between an anode and a cathode, and a second layer is provided between the cathode and the first layer, The second layer has at least one of a structure represented by the following formula (U1) and a structure represented by the following formula (U2): 【Chemistry 1】 (In formulas (U1) to (U2), R 1 and R 3 each independently represents a substituted or unsubstituted alkylene group having 1 to 10 atoms in the main chain, or a substituted or unsubstituted phenylene group. R 2 represents a single bond, a substituted or unsubstituted alkylene group having 1 to 10 atoms in the main chain, or a substituted or unsubstituted phenylene group. The substituent of the substituted alkylene group is an alkyl group, an aryl group, a hydroxyl group, or a halogen atom. The substituent of the substituted phenylene group is a halogen atom, a nitro group, a cyano group, a hydroxyl group, an alkyl group, or a halogen-substituted alkyl group. R 9 represents a hydrogen atom or an alkyl group. A 1 represents any of the groups represented by the following formulas (A-1) to (A-6). B 1 represents a group represented by any one of the following formulas (B-1) to (B-3). D 1 is a group having 5 to 15 atoms in the main chain, as shown in formula (D) below. E 1 is a divalent group represented by any one of the following formulas (E-1) to (E-3): 【Chemistry 2】 (In formula (A-5), R 10 represents a hydrogen atom or an alkyl group.) 【Chemistry 3】 (In formulas (B-1) to (B-3), R 6 and R 7 each independently represents an alkylene group having 1 to 5 atoms in the main chain, an alkylene group having 1 to 5 atoms in the main chain substituted with an alkyl group having 1 to 5 carbon atoms, an alkylene group having 1 to 5 atoms in the main chain substituted with a benzyl group, an alkylene group having 1 to 5 atoms in the main chain substituted with an alkoxycarbonyl group, or an alkylene group having 1 to 5 atoms in the main chain substituted with a phenyl group. One of the carbon atoms in the main chain of the alkylene group is O, S, NH, or NR 15 (R 15 is an alkyl group. R 2 represents a single bond, a substituted or unsubstituted alkylene group having 1 to 10 atoms in the main chain, or a substituted or unsubstituted phenylene group. The substituent of the substituted alkylene group is an alkyl group, an aryl group, a hydroxyl group, or a halogen atom. The substituent of the substituted phenylene group is a halogen atom, a nitro group, a cyano group, a hydroxyl group, an alkyl group, or a halogen-substituted alkyl group. R 12 represents a hydrogen atom or an alkyl group. Ar 2 represents a substituted or unsubstituted phenylene group. The substituent of the substituted phenylene group is a halogen atom, a nitro group, a hydroxyl group, a cyano group, an alkyl group, or a halogenated alkyl group. A 1 and A 2 represents any of the groups represented by formulas (A-1) to (A-5). E 1 is a divalent group represented by any one of the following formulas (E-1) to (E-3). o, p and q each independently represent 0 or 1, and the sum of o, p and q is 1 or more and 3 or less. The arrow indicates the R 3 ) 【Chemistry 4】 (In formula (D), R 4 , R 5 , R 6 and R 7 each independently represents an alkylene group having 1 to 5 atoms in the main chain, an alkylene group having 1 to 5 atoms in the main chain substituted with an alkyl group having 1 to 5 carbon atoms, an alkylene group having 1 to 5 atoms in the main chain substituted with a benzyl group, an alkylene group having 1 to 5 atoms in the main chain substituted with an alkoxycarbonyl group, or an alkylene group having 1 to 5 atoms in the main chain substituted with a phenyl group. One of the carbon atoms in the main chain of the alkylene group is O, S, NH, or NR 15 (R 15 is an alkyl group. Ar 1 and Ar 2 each independently represents a substituted or unsubstituted phenylene group. The substituent of the substituted phenylene group is a halogen atom, a nitro group, a hydroxyl group, a cyano group, an alkyl group, or a halogenated alkyl group. A 2 represents a group represented by any one of the formulas (A-1) to (A-6). l, m, n, o, p, and q each independently represent 0 or 1, and the sum of l, m, and n, and the sum of o, p, and q are 1 or more and 3 or less. 【Chemistry 5】 (In formulas (E-1) to (E-3), R 101 ~R 106 , R 201 ~R 210 , R 301 ~R 304 R each independently represents a single bond, a hydrogen atom, a cyano group, a nitro group, a halogen atom, an alkoxycarbonyl group, a carboxyl group, a dialkylamino group, a hydroxyl group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heterocyclic group. 101 ~R 106 One or two of R 201 ~R 210 One or two of R 301 ~R 304 One or two of represent a single bond. The substituent of the substituted alkyl group is an alkyl group, an aryl group, a halogen atom, or a carbonyl group. The substituent of the substituted aryl group or the substituted heterocyclic group is a halogen atom, a nitro group, a cyano group, an alkyl group, a halogen-substituted alkyl group, an alkoxy group, or a carbonyl group.

2. The above D 1 2. The photoelectric conversion element according to claim 1, wherein: is a group having 10 to 15 atoms in its main chain.

3. The R 4 , R 5 , R 6 and R 7 and each independently represent an alkylene group having 1 to 5 atoms in its main chain, or an alkylene group having 1 to 5 atoms in its main chain substituted with a methyl group or an ethyl group.

4. The Ar 1 and Ar 2 4. The photoelectric conversion element according to claim 1, wherein: is an unsubstituted phenylene group.

5. A photoelectric conversion module comprising a first photoelectric conversion element and a second photoelectric conversion element, wherein at least one of the first and second photoelectric conversion elements is a photoelectric conversion element according to any one of claims 1 to 4.

6. A photoelectric conversion device comprising: the photoelectric conversion element according to claim 1 ; and a power storage section connected to the photoelectric conversion element.

7. A photoelectric conversion device comprising: the photoelectric conversion element according to claim 1 ; and an inverter connected to the photoelectric conversion element.

8. A moving object comprising: the photoelectric conversion element according to claim 1 ; and a body having the photoelectric conversion element.

9. A building material comprising: the photoelectric conversion element according to claim 1 ; and a protective member or a heat dissipating member for protecting the photoelectric conversion element.

Citation Information

Patent Citations

  • Method for producing alizarin derivative compound, new alizarin derivative compound, surface modification method, photoelectric conversion film, photoelectric conversion element, and electrophotographic photoreceptor

    JP2011140478A

  • Electrophotographic photoreceptor, process cartridge, and electrophotographic device

    JP2014029485A

  • Organic inorganic NANO hybrid photoelectric conversion apparatus

    JP2014175472A

  • Solar cell

    JP2019165144A

  • Photoelectric conversion element, photoelectric conversion element module, organic thin-film solar cell, electronic device, and power supply module

    JP2020025068A